Separator for power storage device and power storage device including same

The power storage device separator with a polyolefin micro-porous membrane and protruding inorganic filler particles addresses uneven thickness and adhesion issues, enhancing electrode adhesion and reducing thermal contraction for improved safety and performance.

JP7625008B2Active Publication Date: 2025-01-31ASAHI KASEI BATTERY SEPARATOR CORP

Patent Information

Application Number
JP2022565513
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-11-30
Filing Date
2021-11-30
Publication Date
2025-01-31
Estimated Expiration
2041-11-30

AI Technical Summary

Technical Problem

Existing separators for power storage devices face issues with uneven thickness distribution, poor adhesion to electrodes, inadequate heat resistance, and insufficient suppression of powder falling during manufacturing, leading to decreased adhesive force and increased thermal contraction.

Method used

A power storage device separator featuring a polyolefin micro-porous membrane with a coating layer containing inorganic fillers and thermoplastic polymer particles, where the particles protrude from the coating layer to enhance adhesion and reduce thermal shrinkage, with specific ratios and configurations to ensure uniform distribution and high adhesion.

Benefits of technology

The separator achieves high adhesion to electrodes with a low thermal shrinkage rate, improving cycle characteristics and safety by maintaining structural integrity under high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625008000009
    Figure 0007625008000009
  • Figure 0007625008000010
    Figure 0007625008000010
  • Figure 0007625008000001
    Figure 0007625008000001
Patent Text Reader

Abstract

The present disclosure provides: a separator which is for a power storage device and has high adhesive force to an electrode and a small thermal shrinkage rate; and a power storage device including the same. A separator for a power storage device according to the present disclosure comprises: a base material of a polyolefin microporous film; and a coating layer disposed on at least one surface of the base material, wherein the coating layer contains an inorganic filler and a particulate polymer protruding to a position that corresponds to at least 0.1 times the thickness of the coating layer. The separator for a power storage device has one or more among the following characteristics: the coating layer is formed into an inclined shape so that the thickness of the coating layer increases toward the protruded particulate polymer; at least 20% of the protruded particulate polymer is in contact with the surface of the base material; the 180º peel strength of the coating layer from the base material is at least 200 gf / cm; the average number of adjacent protruded particulate polymers is less than 2; and the ratio of the average particle diameter of the protruded particulate polymer to the average particle diameter of the inorganic filler is greater than 10.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a separator for an electricity storage device and an electricity storage device including the same. [Background technology]

[0002] The development of power storage devices, typified by lithium-ion secondary batteries, is actively underway. In general, a power storage device includes a positive electrode, a negative electrode, and a microporous membrane separator between them. The separator has the function of preventing direct contact between the positive electrode and the negative electrode and allowing ions to pass through the electrolyte held in the micropores. The separator is required to have safety performance, such as a characteristic (fuse characteristic) that quickly stops the battery reaction when abnormally heated, and a performance (short-circuit resistance characteristic) that maintains its shape even at high temperatures and prevents dangerous situations in which the positive electrode and the negative electrode directly react with each other.

[0003] In recent years, in order to increase the capacity of an electricity storage device, the volume of the electricity storage device has been reduced by hot pressing a laminate of an electrode and a separator, or by hot pressing a wound body obtained by winding a laminate of an electrode and a separator. In this case, in order to fix the electrode and the separator after the hot pressing and maintain the volume at the time of pressing, a technique is known in which a coating layer containing a thermoplastic polymer that exhibits an adhesive function under certain conditions is placed on the separator to improve the adhesion between the separator and the electrode.

[0004] For example, Patent Document 1 describes a separator having a porous coating layer containing organic polymer particles for the purpose of enhancing safety by increasing the bonding strength between the separator and the electrodes and by strongly integrating the separator and the electrodes without performing a humidification phase separation process of an organic binder polymer or a secondary coating of an adhesive layer. In this separator, the organic polymer particles protrude to a height of 0.1 μm to 3 μm from the surface of the porous coating layer.

[0005] Patent Document 2 describes a separator with a surface coating containing polymer binder particles of different particle sizes for the purpose of suppressing deformation of the electricity storage device due to the volume expansion of the electrodes during charging. The polymer binder particles of different particle sizes form voids between the separator and the electrodes that allow internal expansion of the electricity storage device.

[0006] Patent Document 3 describes a separator having a composite coating containing inorganic particles, polymer particles and a binder, for the purpose of further improving existing separators and their manufacturing methods, with good thermal stability and good adhesion to electrodes, thereby ensuring the safety and flatness of the power storage device. The polymer particles are dispersed in the inorganic particles and protrude from the surfaces of the inorganic particles.

[0007] Patent Document 4 describes a separator having a functional layer containing inorganic particles and a particulate polymer, with the aim of improving the adhesion, heat resistance, and electrolyte injection property. When the surface of this functional layer is viewed in plan, the ratio of the area occupied by the inorganic particles per unit area of ​​the surface of the functional layer is more than 90%, and the volume average particle diameter of the particulate polymer is within a specific range and is larger than the thickness of the inorganic particle layer.

[0008] Patent Document 5 describes a separator having a functional layer containing inorganic particles and a particulate polymer, with the aim of providing a functional layer for an electrochemical device that has excellent process adhesion and can cause an electrochemical device to exhibit excellent cycle characteristics. This functional layer has a particle-shedding portion, and when the surface of the functional layer for an electrochemical device is viewed in plan, the ratio of the area of ​​the particle-shedding portion to the total area of ​​the particulate polymer and the particle-shedding portion is 0.1% to 40.0%, and the volume average particle diameter of the particulate polymer is larger than the thickness of the inorganic particle layer containing the inorganic particles. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Korean Patent Publication No. 10-2016-0118979 [Patent Document 2] International Publication No. 2019 / 089492 [Patent Document 3] Chinese Patent No. 105958000 [Patent Document 4] International Publication No. 2020 / 175079 [Patent Document 5] International Publication No. 2021 / 085144 Summary of the Invention [Problem to be solved by the invention]

[0010] However, in Patent Document 1 and Patent Document 3, secondary particle-like adhesive polymers are used, and there is a problem that the distribution of the separator thickness is not uniform. Furthermore, since the adhesive polymer has poor dispersibility in the paint state, there are parts on the separator where the adhesive polymer aggregates, and there are problems that the adhesive strength with the electrode is uneven, which reduces the overall adhesive strength and causes deterioration of heat resistance. In Patent Document 2, there is a problem that the heat-resistant layer having an inorganic filler is not provided, and sufficient heat resistance cannot be imparted to the separator. In Patent Documents 4 and 5, the binding strength of the coating layer is insufficient, and there is still room for improvement in suppressing powder fall during the manufacturing process and in adhesive strength with the electrode. One of the objects of the present disclosure is to provide a separator for an electric storage device that has high adhesive strength with the electrode and small thermal shrinkage rate, and an electric storage device including the same, in response to the above separator problems. [Means for solving the problem]

[0011] Examples of embodiments of the present disclosure are listed below. [1] A separator for an electricity storage device, comprising: a substrate which is a polyolefin microporous film containing a polyolefin as a main component; and a coating layer disposed on at least one surface of the substrate, The coating layer includes an inorganic filler and a particulate polymer of a thermoplastic polymer, In the coating layer, the amount of the particulate polymer is 1 part by mass or more and 50 parts by mass or less with respect to 100 parts by mass of the inorganic filler contained in the coating layer, the particulate polymer includes particulate polymer protruding from the coating layer by 0.1 times or more the thickness of the inorganic filler portion of the coating layer, The separator for an electricity storage device, wherein the coating layer is formed in an inclined shape so as to become thicker toward the protruding particulate polymer. [2] 2. The separator for an electricity storage device according to item 1, wherein, when a thickness of an inorganic filler portion of the coating layer is L1 and a maximum distance from a boundary line between the substrate and the coating layer to an outer surface of the inorganic filler of the coating layer formed on the slope is L2, an average value of a slope ratio L2 / L1 of the coating layer is 1.2 or more. [3] 3. The separator for an electricity storage device according to item 1 or 2, wherein an average value of a coverage rate (L2-L1) / (L3-L1) of the protruding portions of the protruding particulate polymer is 0.4 or more, where L1 is a thickness of the inorganic filler portion of the coating layer, L2 is a maximum distance from the substrate-coating layer boundary to an outer surface of the inorganic filler of the coating layer formed on the inclination, and L3 is a maximum distance from the substrate-coating layer boundary to an outline of the protruding particulate polymer. [4] A separator for an electricity storage device, comprising: a substrate which is a polyolefin microporous film containing a polyolefin as a main component; and a coating layer disposed on at least one surface of the substrate, The coating layer includes an inorganic filler and a particulate polymer of a thermoplastic polymer, In the coating layer, the amount of the particulate polymer is 1 part by mass or more and 50 parts by mass or less with respect to 100 parts by mass of the inorganic filler contained in the coating layer, the particulate polymer includes particulate polymer protruding from the coating layer by 0.1 times or more the thickness of the inorganic filler portion of the coating layer, A separator for an electricity storage device, wherein 20% or more of the protruding particulate polymer are in contact with a surface of the substrate. [5] A separator for an electricity storage device, comprising: a substrate which is a polyolefin microporous film containing a polyolefin as a main component; and a coating layer disposed on at least one surface of the substrate, The coating layer includes an inorganic filler and a particulate polymer of a thermoplastic polymer, In the coating layer, the amount of the particulate polymer is 1 part by mass or more and 50 parts by mass or less with respect to 100 parts by mass of the inorganic filler contained in the coating layer, the particulate polymer includes particulate polymer protruding from the coating layer by 0.1 times or more the thickness of the inorganic filler portion of the coating layer, The separator for an electricity storage device, wherein the coating layer has a 180° peel strength from the substrate of 200 gf / cm or more. [6] A separator for an electricity storage device, comprising: a substrate which is a polyolefin microporous film containing a polyolefin as a main component; and a coating layer disposed on at least one surface of the substrate, The coating layer includes an inorganic filler and a particulate polymer of a thermoplastic polymer, In the coating layer, the amount of the particulate polymer is 1 part by mass or more and 50 parts by mass or less with respect to 100 parts by mass of the inorganic filler contained in the coating layer, the particulate polymer includes particulate polymer protruding from the coating layer by 0.1 times or more the thickness of the inorganic filler portion of the coating layer, A separator for an electricity storage device, wherein the average number of the protruding particulate polymers adjacent to any one of the protruding particulate polymers is less than two. [7] A separator for an electricity storage device, comprising: a substrate which is a polyolefin microporous film containing a polyolefin as a main component; and a coating layer disposed on at least one surface of the substrate, The coating layer includes an inorganic filler and a particulate polymer of a thermoplastic polymer, In the coating layer, the amount of the particulate polymer is 1 part by mass or more and 50 parts by mass or less with respect to 100 parts by mass of the inorganic filler contained in the coating layer, the particulate polymer includes particulate polymer protruding from the coating layer by 0.1 times or more the thickness of the inorganic filler portion of the coating layer, A separator for an electricity storage device, wherein a ratio of an average particle size of the protruding particulate polymer to an average particle size of the inorganic filler is greater than 10. [8] 8. The separator for an electricity storage device according to any one of items 1 to 7, wherein the number of the protruding particulate polymers is 50% or more of the total number of the particulate polymers contained in the coating layer. [9] 9. The separator for an electricity storage device according to any one of items 1 to 8, wherein the number of other protruding particulate polymers present within a radius of 10 μm from any one of the protruding particulate polymers is less than 60.

[10] 10. The separator for an electricity storage device according to any one of items 1 to 9, wherein the separator for an electricity storage device has a methylene chloride soluble content of 0.05 parts by mass or more and 0.80 parts by mass or less with respect to the total mass of the separator for the electricity storage device.

[11] 11. The separator for an electricity storage device according to any one of items 1 to 10, wherein the total amount of metal cations contained in the coating layer is 0.1 ppm or more and 100 ppm or less based on the total mass of the coating layer.

[12] 12. The separator for an electricity storage device according to any one of items 1 to 11, wherein the coating layer contains a water-soluble polymer.

[13] Item 13. The separator for use in an electricity storage device according to item 12, wherein the content of the water-soluble polymer is 0.04 parts by mass or more and less than 2 parts by mass per 100 parts by mass of the inorganic filler.

[14] 14. The separator for an electricity storage device according to any one of items 1 to 13, wherein the thickness of one of the coating layers disposed on at least one of the substrates is 0.3 μm or more and 1.3 μm or less.

[15] 15. The separator for an electricity storage device according to any one of items 1 to 14, wherein the particulate polymer comprises at least one selected from the group consisting of a copolymer containing a (meth)acrylate as a monomer, a styrene-butadiene copolymer, and a copolymer containing a fluorine atom.

[16] 16. The separator for an electricity storage device according to any one of items 1 to 15, wherein the particulate polymer comprises a copolymer containing (meth)acrylic acid, butyl (meth)acrylate, and ethylhexyl (meth)acrylate as monomers.

[17] 17. The electricity storage device separator according to any one of items 1 to 16, wherein the particulate polymer comprises a copolymer containing a polyfunctional (meth)acrylate as a monomer.

[18] 18. The separator for an electricity storage device according to any one of items 1 to 17, wherein the particulate polymer is a primary particle.

[19] Item 19. The separator for use in an electricity storage device according to item 18, wherein the primary particles have an average particle size of 1 μm or more and 10 μm or less.

[20] 20. The separator for an electricity storage device according to any one of items 1 to 19, which has a thermal shrinkage rate in the TD direction at 130° C. for 1 hour of 5% or less. [twenty one] 21. The separator for an electricity storage device according to any one of items 1 to 20, which has a thermal shrinkage rate in the TD direction at 150° C. for 1 hour of 5% or less. [twenty two] 22. An electricity storage device comprising the separator for an electricity storage device according to any one of items 1 to 21. Effect of the Invention

[0012] According to the present disclosure, there are provided a separator for an electricity storage device that has high adhesive strength with electrodes and a small thermal shrinkage rate, and an electricity storage device including the same. [Brief description of the drawings]

[0013] [Figure 1]2 is a schematic diagram of the surface of a coating layer of the electricity storage device separator of the present embodiment. FIG. [Diagram 2] FIG. 2 is a schematic diagram of a cross section taken along line AA in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an exemplary embodiment of the present disclosure (hereinafter, abbreviated as "the present embodiment") will be described in detail, but the present disclosure is not limited to the present embodiment.

[0015] <Separator for power storage device> The separator for an electricity storage device of this embodiment includes a substrate that is a microporous polyolefin film containing polyolefin as a main component, and a coating layer disposed on at least one surface of the substrate. The coating layer includes an inorganic filler and a particulate polymer of a thermoplastic polymer.

[0016] <Amount of Particulate Polymer> The amount of the particulate polymer is 1 part by mass or more and 50 parts by mass or less, preferably 3 parts by mass or more and 50 parts by mass or less, more preferably 5 parts by mass or more and 30 parts by mass or less, and even more preferably 10 parts by mass or more and 25 parts by mass or less, relative to 100 parts by mass of the inorganic filler. By using the particulate polymer in an amount of 1 part by mass or more and 50 parts by mass or less, it is possible to increase the adhesive strength with the electrode while maintaining ion permeability. In addition, from the viewpoint of improving heat shrinkage resistance, 10 parts by mass or less is preferable.

[0017] <Protruding Amount of Particulate Polymer> The particulate polymer includes particulate polymer protruding from the coating layer by 0.1 times or more the thickness of the inorganic filler part of the coating layer. The "thickness of the inorganic filler part of the coating layer" means the distance between the surface of the polyolefin microporous film and the outermost surface of the layer (layer of inorganic filler) in which inorganic fillers are stacked on the surface of the polyolefin microporous film, and is measured from an SEM image of the cross section of the coating layer. The "inorganic filler part" means a part that does not contain particulate polymer and is 1.5D or more away from the center of each protruding particulate polymer in the horizontal direction (the surface direction of the coating layer) when the diameter of each protruding particulate polymer is D. The measurement conditions are explained in the column of the examples. The protrusion of the particulate polymer is 0.1 times or more the thickness of the inorganic filler part of the coating layer, so that the adhesive force with the electrode can be increased. In addition, the protrusion of the particulate polymer is 0.1 times or more the thickness of the inorganic filler part of the coating layer, so that a gap is formed between the separator and the electrode. The voids can mitigate the effect of internal expansion accompanying charging and discharging of the electricity storage device, suppress distortion of the wound body, and improve cycle characteristics. From this viewpoint, the protrusion of the particulate polymer is preferably 0.2 times or more, and more preferably 0.3 times or more. From the viewpoint of suppressing the particulate polymer from falling off the separator, the protrusion of the particulate polymer is preferably 5 times or less, more preferably 4 times or less, 3 times or less, 2 times or less, 1 time or less, or 0.4 times or less.

[0018] In the present specification, "protruding" means that the particulate polymer protrudes toward the surface side of the coating layer beyond the "thickness of the inorganic filler portion of the coating layer". In the protruding portion of the particulate polymer (hereinafter referred to as "protruding portion"), the particulate polymer does not need to be exposed on the surface of the coating layer, and at least a part or all of the protruding portion may be covered with an inorganic filler. From the viewpoint of preventing the particulate polymer from slipping off the coating layer and obtaining a higher adhesive strength, it is preferable that at least a part of the periphery of the protruding portion is covered with an inorganic filler. In addition, from the viewpoint of ensuring the contact area between the particulate polymer and the electrode and obtaining a higher adhesive strength, it is preferable that the center of the protruding portion is exposed on the surface of the coating layer.

[0019] <Gradient morphology of coating layer, contact ratio between particulate polymer and substrate, 180° peel strength, average number of adjacent particulate polymer particles, and average particle size ratio> The separator for a power storage device of this embodiment has one or more of the following characteristics (1) to (5): (1) the coating layer is formed in an inclined shape so that it becomes thicker toward the protruding particulate polymer; (2) 20% or more of the protruding particulate polymers are in contact with the surface of the substrate; (3) the 180° peel strength of the coating layer from the substrate (hereinafter also simply referred to as "180° peel strength") is 200 gf / cm or more; (4) the average number of protruding particulate polymers adjacent to any one protruding particulate polymer (hereinafter also simply referred to as "average number of adjacent particulate polymers") is less than two; (5) the ratio of the average particle diameter of the protruding particulate polymer to the average particle diameter of the inorganic filler, i.e., the ratio calculated by the average particle diameter of the particulate polymer / the average particle diameter of the inorganic filler (hereinafter also simply referred to as "average particle diameter ratio") is greater than 10. By having at least one of the above characteristics (1) to (5), a separator for a power storage device having high adhesion to an electrode and low thermal shrinkage can be provided.

[0020] Feature(1): In the first embodiment of the separator for an electric storage device, the coating layer is formed in a sloping shape so that it becomes thicker toward the protruding particulate polymer. This prevents the particulate polymer from slipping off the coating layer, and increases the adhesive strength with the electrode. In the present specification, the term "sloping shape" means that, when the thickness of the inorganic filler part of the coating layer is L1 and the maximum distance from the substrate-coating layer boundary to the outer surface of the inorganic filler of the coating layer formed on the slope is L2, the average value of the slope ratio L2 / L1 of the coating layer is 1.1 or more. For an example of the relationship between L1 and L2, please refer to the schematic diagram of FIG. 2. The slope is preferably such that the thickness of the coating layer changes continuously so that the coating layer gradually becomes thicker toward the protruding particulate polymer, and preferably does not include discontinuous changes due to missing of the coating layer. The absence of missing of the coating layer tends to improve heat resistance and cycle characteristics. The slope may be gentler as it moves away from the protruding particulate polymer, and may be steeper as it approaches the protruding part of the protruding particulate polymer. Also, if the inorganic filler covers at least a part or all of the protruding portion, the slope on the protruding portion may become gentler again toward the center of the protruding portion. The average value of the slope ratio L2 / L1 of the coating layer is preferably 1.2 or more, 1.3 or more, 1.4 or more, 1.5 or more, or 1.7 or more.

[0021] The coating layer may be formed in an inclined manner so that it becomes thicker toward the protruding particulate polymer, and the inorganic filler may cover at least a part or all of the protruding portion so as to ride along the contour of the particulate polymer. The inorganic filler preferably covers a part of the periphery of the protruding portion so as to ride along the contour of the particulate polymer. In addition, it is preferable that the vicinity of the center of the protruding portion is exposed on the surface of the coating layer. If the maximum distance from the substrate-coating layer boundary to the contour of the protruding particulate polymer (the distance from the substrate-coating layer boundary to the point on the contour of the protruding particulate polymer that is the furthest from the substrate-coating layer boundary) is L3, the average value of the coverage rate (L2-L1) / (L3-L1) of the protruding portion is preferably 0.4 or more. For an example of the relationship between L1, L2, and L3, please refer to the schematic diagram in FIG. 2. By the average value of the inclination rate L2 / L1 being 1.1 or more, or the average value of the coverage rate (L2-L1) / (L3-L1) being 0.4 or more, the particulate polymer is prevented from slipping off the coating layer, and the adhesion to the electrode is increased. The upper limit of the average value of the gradient ratio L2 / L1 is not particularly limited, but may be 5.0 or less, 4.0 or less, 3.0 or less, 2.8 or less, 2.5 or less, 2.3 or less, 2.0 or less, or 1.8 or less, from the viewpoint of securing the adhesion area between the particulate polymer and the electrode and enhancing the adhesion force with the electrode. The upper limit of the coverage ratio (L2-L1) / (L3-L1) is preferably less than 1.0, 0.9 or less, 0.8 or less, or 0.7 or less. A coverage ratio of 1.0 or more means that the inorganic filler on the protruding portion of the particulate polymer reaches the top of the outline of the protruding particulate polymer (the point farthest from the boundary line between the substrate and the coating layer). When the coverage ratio is less than 1.0, the contact area between the particulate polymer and the electrode is secured, and the adhesion force with the electrode is enhanced. When the coverage ratio is 0.8 or less, the contact area between the particulate polymer and the electrode is larger, and the adhesion force with the electrode is enhanced.

[0022] Feature(2): In the second embodiment of the separator for an electric storage device, the contact rate between the particulate polymer protruding from the coating layer in the coating layer and the surface of the substrate is 20% or more, preferably 50% or more, and more preferably 70% or more. The "contact rate" is calculated from an image of the cross section of the coating layer of the separator for an electric storage device observed with an SEM. By increasing the amount of particulate polymer protruding from the coating layer and in contact with the substrate, the binding strength between the substrate and the particulate polymer is further increased, the 180° peel strength is improved, and the adhesive strength with the electrode is increased. The upper limit of the contact rate between the particulate polymer protruding from the coating layer in the coating layer and the surface of the substrate is not particularly limited, but may be less than 100% or 100%.

[0023] Feature(3): In the third embodiment, the separator for an electricity storage device has a 180° peel strength of 200 gf / cm or more, preferably 230 gf / cm or more, and more preferably 250 gf / cm or more. The "180° peel strength" refers to the strength when the coating layer is peeled off so that the surface of the coating layer facing the substrate forms an angle of 180° with the substrate. When the 180° peel strength is 200 gf / cm or more, the adhesive strength with the electrode is increased and thermal shrinkage is suppressed. The upper limit of the 180° peel strength is not particularly limited, but may be 500 gf / cm or less.

[0024] Feature(4): In the fourth embodiment of the separator for a power storage device, the average number of adjacent particulate polymers is less than 2, preferably less than 1. "Adjacent" means that the shortest distance between the outer edge of a particulate polymer and the outer edge of another particulate polymer is 0.2 μm or less in an image obtained by observing the surface of the coating layer of the separator for a power storage device with an SEM. The average number of adjacent particulate polymers being less than 2 means that the particulate polymers are uniformly dispersed in the coating layer, which improves the 180° peel strength, increases the adhesive strength with the electrode, suppresses thermal shrinkage, and ensures the uniformity of the thickness of the coating layer. The lower limit of the average number of adjacent particulate polymers is not particularly limited, but may be greater than 0 or 0.

[0025] Feature(5): In the fifth embodiment of the separator for an electric storage device, the ratio of the average particle diameter of the protruding particulate polymer to the average particle diameter of the inorganic filler is greater than 10. Each "average particle diameter" is measured from an image of the surface of the coating layer of the separator for an electric storage device observed with a SEM. The measurement conditions are explained in the Examples section. When the ratio of the average particle diameter is greater than 10, the particulate polymer is likely to form a structure protruding from the surface of the coating layer, and therefore the adhesive strength with the electrode is increased and thermal shrinkage is suppressed. From the viewpoint of achieving both the permeability and adhesive strength of the separator, the upper limit of the ratio of the average particle diameter is preferably 50 or less, more preferably 35 or less, and even more preferably 25 or less, 22 or less, or 20 or less.

[0026] The separator for an electricity storage device of this embodiment may have any combination of the above characteristics (1) to (5), i.e., (1) and (2); (1) and (3); (1) and (4); (1) and (5); (2) and (3); (2) and (4); (2) and (5); (3) and (4); (3) and (5); (4) and (5); (1), (2) and (3); (1), (2) and (4); (1), (2) and (5); (1), (3) and (4); (1), ( (3) and (5); (1), (4) and (5); (2), (3) and (4); (2), (3) and (5); (2), (4) and (5); (3), (4) and (5); (1), (2), (3) and (4); (1), (2), (3) and (5); (1), (2), (4) and (5); (1), (3), (4) and (5); (2), (3), (4) and (5); or combinations of (1), (2), (3), (4) and (5). Among these, from the viewpoint of higher adhesive strength and smaller thermal shrinkage, the combination of (1), (2) and (3) is preferred, i.e., the coating layer is formed in an inclined shape so that it becomes thicker toward the protruding particulate polymer, the contact rate between the particulate polymer protruding from the coating layer and the substrate surface is 20% or more, and the 180° peel strength is 200 gf / cm or more.

[0027] <Number of polymer particles within a radius of 10 μm> In the separator for an electric storage device of this embodiment, the number of other protruding particulate polymers present within a radius of 10 μm from any one protruding particulate polymer is preferably less than 60, more preferably less than 40, even more preferably less than 15, and even more preferably less than 5. This makes it possible to suppress variation in adhesive strength. The lower limit of the number of particulate polymers within a radius of 10 μm is not particularly limited and may be 0, but may be 1 or more in order to appropriately dense the particulate polymers and improve adhesive strength.

[0028] <Methylene chloride solubles> In the separator for an electric storage device of this embodiment, the methylene chloride soluble content is preferably 0.05 parts by mass or more and 0.80 parts by mass or less, more preferably 0.10 parts by mass or more and 0.60 parts by mass or less, and even more preferably 0.15 parts by mass or more and 0.50 parts by mass or less, based on the total mass of the separator for an electric storage device. The "soluble content" of methylene chloride means a component extracted into methylene chloride when the separator is immersed in methylene chloride. The plasticizer mixed when manufacturing the substrate is mainly extracted as the methylene chloride soluble content. By containing 0.10 parts by mass or more of methylene chloride soluble content, the binding strength between the substrate and the coating layer is further increased, and it is easier to adjust the 180° peel strength to 200 gf / cm or more. By having the methylene chloride soluble content of 0.60 parts by mass or less, the internal resistance of the battery can be reduced. Methods for adjusting the methylene chloride solubles to 0.05 parts by mass or more and 0.80 parts by mass or less in the plasticizer extraction process during base material production include adjusting the extraction time, type of extraction solvent, temperature of the extraction solvent, number of extractions, etc. if the process is a batch type, and adjusting the extraction time, type of extraction solvent, temperature of the extraction solvent, amount of extraction solvent supplied, etc. if the process is a continuous type.

[0029] <Metal cation> In the separator for an electric storage device of this embodiment, the total amount of metal cations contained in the coating layer is preferably 0.1 ppm or more and 100 ppm or less, more preferably 0.1 ppm or more and 70 ppm or less, and even more preferably 0.1 ppm or more and 50 ppm or less, based on the total mass of the coating layer. When the total amount of metal cations is adjusted to a low amount, the inorganic filler and the particulate polymer are easily uniformly dispersed and applied in the formation of the coating layer. As the metal cation, sodium ions (Na + ), calcium ion (Ca 2+ ) and magnesium ions (Mg 2+ ) and the like. One method for adjusting the total amount of metal cations to 0.1 ppm or more and 100 ppm or less is to wash the filler, which is the raw material for the coating layer, with water before use. The number of washings may be one or more than two, but the more washings are performed, the lower the total amount of metal cations contained in the filler.

[0030] <Heat shrinkage rate> The separator for an electric storage device of this embodiment has a thermal shrinkage rate in the TD direction at 130°C for 1 hour of 5% or less, more preferably 0% to 3% or less, and even more preferably 0% to 1% or less. More preferably, the thermal shrinkage rate in the TD direction at 150°C for 1 hour is 5% or less, more preferably 0% to 3% or less, and even more preferably 0% to 1% or less. Here, if the thermal shrinkage rate in the TD direction is 5% or less, it is possible to more effectively suppress the occurrence of a short circuit at a location other than the location to which an external force is applied when heat is generated due to a short circuit during a crash test. This makes it possible to more reliably prevent the temperature rise of the entire battery, and the smoke and fire that may occur as a result of the short circuit. The thermal shrinkage rate of the separator can be adjusted by appropriately combining the stretching operation and heat treatment of the base material described above. It is preferable that the thermal shrinkage rate in the TD direction is suppressed and at the same time, the thermal shrinkage in the MD direction is also 5% or less. The thermal shrinkage in the MD direction is more preferably 0% to 3% or less, and even more preferably 0% to 1% or less.

[0031] <Air permeability of separator> The air permeability of the separator for the electricity storage device is preferably 10 seconds / 100 cm 3 More than 10000 seconds / 100cm 3 More preferably, it is 10 seconds / 100 cm or less. 3 More than 1000 seconds / 100cm 3 More preferably, it is 50 seconds / 100 cm or less. 3 More than 500 seconds / 100cm 3 More preferably, it is 80 seconds / 100 cm or less. 3 More than 250 seconds / 100cm 3 This results in high ion permeability. The air permeability is the air resistance measured in accordance with JIS P-8117.

[0032] <Base material> (Substrate material) The separator for the electric storage device of this embodiment has a substrate which is a polyolefin microporous film containing polyolefin as a main component. "Containing as a main component" means that the target component (polyolefin) is more than 50 parts by mass with respect to the reference mass (total mass of the substrate). The content of polyolefin in the polyolefin microporous film is preferably 75 parts by mass or more, more preferably 85 parts by mass or more, even more preferably 90 parts by mass or more, even more preferably 95 parts by mass or more, particularly preferably 98 parts by mass or more, and may be 100 parts by mass. When a coating liquid is applied onto the film, polyolefin has excellent coatability of the coating liquid, which is advantageous for making the thickness of the separator thinner, and the active material ratio in the electric storage device can be increased, thereby increasing the capacity per volume. The polyolefin microporous film can be one that has been used as a substrate for conventional separators, and is preferably a porous film with a fine pore size that is non-electron conductive, ion conductive, and highly resistant to organic solvents.

[0033] The polyolefin is not particularly limited, and may be a polyolefin that can be used in normal extrusion, injection, inflation, and blow molding, etc. Examples of polyolefins include homopolymers containing ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, etc. as monomers, as well as copolymers and multi-stage polymers of two or more of these monomers. These homopolymers, copolymers, and multi-stage polymers may be used alone or in combination of two or more.

[0034] Examples of polyolefins include polyethylene, polypropylene, and polybutene, and more specifically, low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, high-density polyethylene, ultra-high molecular weight polyethylene, isotactic polypropylene, atactic polypropylene, ethylene-propylene random copolymer, polybutene, and ethylene-propylene rubber. These may be used alone or in combination of two or more. Among these, the polyolefin is preferably at least one selected from the group consisting of low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, high-density polyethylene, and ultra-high molecular weight polyethylene, from the viewpoint of shutdown characteristics in which pores are closed by thermal melting. In particular, high-density polyethylene is preferred because of its low melting point and high strength, and has a density of 0.93 g / cm as measured according to JIS K 7112. 3 More preferred are polyethylenes having a molecular weight of 50 parts by mass or more. The polymerization catalyst used in the production of these polyethylenes is not particularly limited, but examples thereof include Ziegler-Natta catalysts, Phillips catalysts, and metallocene catalysts. It is preferred that the main component of the polyolefin is polyethylene, and the content of polyethylene relative to the total mass of the polyolefin in the substrate is preferably 50 parts by mass or more.

[0035] In order to improve the heat resistance of the substrate, the polyolefin microporous film preferably contains polypropylene and polyolefin other than polypropylene. Examples of polyolefin resin other than polypropylene include homopolymers with ethylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, etc. as monomers, copolymers of two or more of these monomers, and multi-stage polymers.

[0036] The amount of polypropylene relative to the total mass of polyolefin in the substrate (polypropylene / polyolefin) is not particularly limited, but from the viewpoint of achieving both heat resistance and good shutdown function, it is preferably 1 to 35 parts by mass, more preferably 3 to 20 parts by mass, and even more preferably 4 to 10 parts by mass. From the same viewpoint, the content ratio of olefin resin other than polypropylene, such as polyethylene, relative to the total mass of polyolefin in the polyolefin microporous membrane (olefin resin other than polypropylene / polyolefin) is preferably 65 to 99 parts by mass, more preferably 80 to 97 parts by mass, and even more preferably 90 to 96 parts by mass.

[0037] The viscosity average molecular weight of the polyolefin, which is the main component of the substrate, is not particularly limited, but is preferably 30,000 to 12 million, more preferably 50,000 to less than 2 million, and even more preferably 100,000 to less than 1 million. When the viscosity average molecular weight is 30,000 or more, the melt tension during melt molding becomes large, which improves moldability, and the strength tends to be further increased due to entanglement between polymers. On the other hand, when the viscosity average molecular weight is 12 million or less, it is preferable because it is easy to uniformly melt-knead, and the moldability of the sheet, especially the thickness stability, tends to be excellent. Furthermore, when the viscosity average molecular weight is less than 1 million, it is preferable because it tends to block holes when the temperature rises and to obtain a better shutdown function. The viscosity average molecular weight (Mv) is calculated from the intrinsic viscosity [η] measured at a measurement temperature of 135 ° C. using decalin as a solvent based on ASTM-D4020 according to the following formula. Polyethylene: [η] = 6.77 × 10-4 Mv 0.67 (Chiang's formula) Polypropylene: [η] = 1.10 × 10 -4 Mv 0.80 For example, instead of using a polyolefin having a viscosity average molecular weight of less than 1 million alone, a mixture of a polyolefin having a viscosity average molecular weight of 2 million and a polyolefin having a viscosity average molecular weight of 270,000, the viscosity average molecular weight of which is less than 1 million, may be used.

[0038] The substrate may contain other resins besides polyolefin, such as polyethylene terephthalate, polycycloolefin, polyethersulfone, polyamide, polyimide, polyimideamide, polyaramid, polycycloolefin, nylon, and polytetrafluoroethylene.

[0039] The substrate may contain any additive. Such additives are not particularly limited, and examples thereof include plasticizers, polymers other than polyolefins, inorganic particles, antioxidants such as phenols, phosphorus-based, and sulfur-based, metal soaps such as calcium stearate and zinc stearate, ultraviolet absorbers, light stabilizers, antistatic agents, antifogging agents, and coloring pigments. The total content of these additives is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, based on 100 parts by mass of the polyolefin resin in the polyolefin microporous film.

[0040] The substrate preferably contains a plasticizer. When the substrate contains a plasticizer, the adhesive strength between the substrate and the coating layer is improved, and it is easier to control the 180° peel strength to 200 gf / cm or more. The amount of the plasticizer is preferably 0.1 parts by mass or more and 1.6 parts by mass or less, more preferably 0.2 parts by mass or more and 1.2 parts by mass or less, and 0.3 parts by mass or more and 1.0 parts by mass or less, based on the total mass of the substrate. By using the amount of the plasticizer within the above range, the adhesive strength between the substrate and the coating layer can be improved while lowering the internal resistance of the battery. Examples of the plasticizer include hydrocarbons such as liquid paraffin, esters such as dioctyl phthalate and dibutyl phthalate, and higher alcohols such as oleyl alcohol and stearyl alcohol. Among these, the plasticizer is preferably liquid paraffin.

[0041] (Structure of substrate) The porosity of the substrate is not particularly limited, but is preferably 30% to 60%, more preferably 35% to 50%. This allows the coating layer to be appropriately impregnated into the micropores of the substrate, making it easier to control the 180° peel strength to 200 gf / cm or more. The porosity is determined by the volume (cm) of the substrate sample. 3 ), mass (g), membrane density (g / cm 3 ) to the following formula: Porosity = (volume - mass / film density) / volume x 100 Here, for example, in the case of a microporous polyolefin membrane made of polyethylene, the membrane density is 0.95 g / cm 3 The porosity can be adjusted by changing the stretch ratio of the polyolefin microporous membrane, etc.

[0042] The air permeability of the substrate is not particularly limited, but is preferably 10 sec / 100 cm 3 More than 10000 seconds / 100cm 3 More preferably, it is 10 seconds / 100 cm or less. 3 More than 1000 seconds / 100cm 3 More preferably, it is 40 seconds / 100 cm or less. 3 More than 450 seconds / 100cm 3More preferably, it is 70 seconds / 100 cm or less. 3 More than 200 seconds / 100cm 3 This allows the coating layer to be appropriately impregnated into the micropores of the substrate, making it easier to control the 180° peel strength to 200 gf / cm or more. The air permeability is the air resistance measured in accordance with JIS P-8117. The air permeability can be adjusted by changing the stretching temperature and / or stretching ratio of the substrate.

[0043] The average pore size of the substrate is preferably 0.15 μm or less, more preferably 0.1 μm or less, and preferably 0.01 μm or more. The average pore size of 0.15 μm or less is suitable from the viewpoint of suppressing self-discharge of the electricity storage device and suppressing capacity reduction. The average pore size can be adjusted by changing the stretching ratio when manufacturing the substrate.

[0044] The puncture strength of the substrate is not particularly limited, but is preferably 200 gf / 20 μm or more, more preferably 300 gf / 20 μm or more, even more preferably 400 gf / 20 μm or more, and is preferably 2000 gf / 20 μm or less, more preferably 1000 gf / 20 μm or less. A puncture strength of 200 gf / 20 μm or more is preferable from the viewpoint of suppressing film breakage due to fallen active material when the separator is wound together with the electrode, and from the viewpoint of suppressing concerns about short circuit due to expansion and contraction of the electrode accompanying charge and discharge. On the other hand, a puncture strength of 2000 gf / 20 μm or less is preferable from the viewpoint of reducing width shrinkage due to orientation relaxation during heating. The puncture strength is measured according to the method described in the examples. The puncture strength can be adjusted by adjusting the stretch ratio and / or stretching temperature of the substrate.

[0045] The thickness of the substrate is not particularly limited, but is preferably 2 μm or more, more preferably 5 μm or more, even more preferably 6 μm or more, and particularly preferably 7 μm or more, and is preferably 100 μm or less, more preferably 60 μm or less, even more preferably 50 μm or less, and particularly preferably 16 μm or less. A thickness of 2 μm or more is preferable from the viewpoint of improving mechanical strength. On the other hand, a thickness of 100 μm or less is preferable because the volume occupied by the separator in the electricity storage device is reduced, which tends to be advantageous in terms of increasing the capacity of the electricity storage device.

[0046] <Coating layer> The separator for an electric storage device of this embodiment includes a coating layer disposed on at least one surface of the substrate. That is, the coating layer may be disposed on only one surface of the substrate, or on both surfaces. "Disposed on the surface" means that the coating layer may be disposed on the entire surface of the substrate, or on a part of the surface. The coating layer is intended to be directly bonded to the electrode. It is preferable that the coating layer is disposed so that the substrate and the electrode are bonded via the coating layer so that the coating layer is directly bonded to the electrode. The coating layer is preferably a coating layer formed by applying a coating liquid containing an inorganic filler and a particulate polymer to the substrate.

[0047] The coating layer includes an inorganic filler, a particulate polymer of a thermoplastic polymer, and a resin binder. The coating layer may further include a water-soluble polymer and other additives in addition to the particulate polymer of a thermoplastic polymer.

[0048] (Inorganic filler) The inorganic filler is not particularly limited, but is preferably one that has a melting point of 200°C or more, has high electrical insulation, and is electrochemically stable within the range of use of an electricity storage device such as a lithium ion secondary battery. Examples of such inorganic fillers include inorganic oxides (oxide ceramics) such as alumina, silica, titania, zirconia, magnesia, ceria, yttria, zinc oxide, and iron oxide; inorganic nitrides (nitride ceramics) such as silicon nitride, titanium nitride, and boron nitride; ceramics such as silicon carbide, calcium carbonate, magnesium sulfate, aluminum sulfate, barium sulfate, aluminum hydroxide, aluminum oxide hydroxide, potassium titanate, talc, kaolinite, dickite, nacrite, halloysite, pyrophyllite, montmorillonite, sericite, mica, amesite, bentonite, asbestos, zeolite, calcium silicate, magnesium silicate, diatomaceous earth, and silica sand; and glass fibers. These may be used alone or in combination of two or more. Among these, the inorganic filler is preferably at least one selected from the group consisting of alumina, barium sulfate, and aluminum oxide hydroxide (boehmite).

[0049] The lower limit of the average particle size of the inorganic filler is preferably 50 nm or more, 100 nm or more, 150 nm or more, 200 nm or more, 250 nm or more, 300 nm or more, 350 nm or more, or 400 nm or more, and the upper limit is preferably 2000 nm or less, 1100 nm or less, 800 nm or less, 450 nm or less, 400 nm or less, 350 nm or less, or 300 nm or less. The average particle size of the inorganic filler is 50 nm or more, from the viewpoint of maintaining voids for ions to pass through the coating layer and improving the rate characteristics. The average particle size of the inorganic filler is 2000 nm or less, from the viewpoint of increasing the concentration of the inorganic filler in the coating layer and improving the heat shrinkage resistance. The average particle size of the inorganic filler is preferably, for example, 180 nm or more and 300 nm or less. The reason is that, particularly when the thickness of the coating layer is small, a uniform coating layer thickness is formed and the heat shrinkage resistance is improved. It is also preferable that the average particle size of the inorganic filler is, for example, 250 nm or more and 450 nm or less. This is because it is possible to achieve a high degree of compatibility between rate characteristics and heat shrinkage resistance. The "average particle size" of the inorganic filler was measured by the method described in the Examples. As a method for adjusting the particle size and its distribution of the inorganic filler, for example, a method of pulverizing the inorganic filler using an appropriate pulverizing device such as a ball mill, a bead mill, a jet mill, etc. to reduce the particle size can be mentioned. The particle size distribution of the inorganic filler can be made so that there is one peak in a graph of frequency against particle size. However, it may be made so that there are two peaks or a trapezoidal chart with no peak.

[0050] The shape of the inorganic filler may be, for example, plate-like, scaly, needle-like, columnar, spherical, polyhedral, or block-like. A combination of a plurality of inorganic fillers having these shapes may be used. From the viewpoint of improving the gradient of the coating layer and increasing the adhesive strength with the electrode, the block shape is preferable.

[0051] The aspect ratio of the inorganic filler is preferably 1.0 or more and 2.5 or less, more preferably 1.1 or more and 2.0 or less. The aspect ratio of 2.5 or less is preferable from the viewpoint of suppressing the moisture adsorption amount of the multilayer porous film and suppressing the capacity deterioration when cycled, suppressing deformation at a temperature exceeding the melting point of the base material, and improving the gradient rate of the coating layer and increasing the adhesive strength with the electrode. The reason why the gradient rate increases when the aspect ratio of the inorganic filler is 1.0 or more and 2.5 or less is considered to be because the orientation of the particles in the coating layer is small, making it easy to form a laminated structure.

[0052] The particle size distribution of the inorganic filler, which is obtained by dividing the standard deviation SD of the volume average particle size of the inorganic filler by the D50 value, is preferably 0.55 or less, more preferably 0.50 or less, and even more preferably 0.45 or less. A particle size distribution of 0.55 or less is preferable from the viewpoint of suppressing deformation at a temperature exceeding the melting point of the substrate, and from the viewpoint of improving the gradient rate of the coating layer and increasing the adhesive strength with the electrode. The reason why the gradient rate increases when the particle size distribution of the inorganic filler is 0.55 or less is considered to be because the uniformity of the particles is increased and the contact rate between the particles is improved, making it easier to form a laminated structure.

[0053] The amount of the inorganic filler is, for example, 20 parts by mass or more and less than 100 parts by mass, 30 parts by mass or more and 80 parts by mass or less, 35 parts by mass or more and 70 parts by mass or less, or even 40 parts by mass or more and 60 parts by mass or less, based on the total mass of the coating layer.

[0054] (particulate polymer) The particulate polymer is a particle of a thermoplastic polymer. From the viewpoint of enhancing the adhesion between the separator and the electrode, the particulate polymer preferably contains a thermoplastic polymer having a glass transition temperature or melting point of 20°C or more and 200°C or less. The glass transition temperature refers to the midpoint glass transition temperature described in JIS K7121, and is determined from a DSC curve obtained by differential scanning calorimetry (DSC). Specifically, the temperature at the point where a curve of a stepwise change part of the glass transition intersects with a straight line extending the low-temperature side baseline of the DSC curve to the high-temperature side and a straight line equidistant in the vertical axis direction from the straight line extending the high-temperature side baseline of the DSC curve to the low-temperature side can be adopted as the glass transition temperature. More specifically, it may be determined according to the method described in the examples. In addition, the "glass transition" refers to a change in heat flow rate that occurs on the endothermic side due to a change in the state of the polymer, which is a test piece, in DSC. Such a change in heat flow rate is observed as a step-like change in the shape of a DSC curve. The "step-like change" refers to the part of the DSC curve where the curve moves away from the previous low-temperature side baseline and transitions to a new high-temperature side baseline. A step change also includes a combination of a step change and a peak. It can also be expressed as a point where an upwardly convex curve changes to a downwardly convex curve, assuming that the upper side of the step change is the heat generation side. A "peak" refers to the part of a DSC curve where the curve leaves the low-temperature baseline and returns to the same baseline. A "baseline" refers to the DSC curve in the temperature range where no transition or reaction occurs in the test specimen.

[0055] The glass transition temperature (Tg) of the particulate polymer is preferably 20°C or more and 110°C or less, more preferably 50°C or more, even more preferably 80°C or more, and even more preferably 90°C or more, and is particularly preferably greater than 90°C in terms of improving the adhesive strength after injection of the electrolyte. The Tg of the particulate polymer is preferably 20°C or more in terms of preventing adjacent separators from sticking together (blocking) through the coating layer during storage and transportation of the separator for the electric storage device and during the manufacturing process of the electric storage device. On the other hand, the Tg of the particulate polymer is preferably 110°C or less in terms of obtaining good adhesive strength with the electrode. The Tg of the particulate polymer can be appropriately adjusted, for example, by changing the type of monomer used in producing the particulate polymer and the compounding ratio of each monomer when the particulate polymer is a copolymer. That is, for each monomer used in the production of a particulate polymer, the glass transition temperature can be roughly estimated from the Tg of the homopolymer generally shown (for example, as described in "Polymer Handbook" (A WILEY-INTERSCIENCE PUBLICATION)) and the blending ratio of the monomers. For example, the Tg of a copolymer obtained by copolymerizing a high ratio of monomers such as methyl methacrylate, acrylonitrile, and methacrylic acid, which give a homopolymer with a Tg of about 100°C, is high, while the Tg of a copolymer obtained by copolymerizing a high ratio of monomers such as n-butyl acrylate and 2-ethylhexyl acrylate, which give a homopolymer with a Tg of about -50°C, is low. The Tg of a copolymer can also be roughly calculated by the FOX formula represented by the following mathematical formula (1). 1 / Tg=W1 / Tg1+W2 / Tg2+···+W i / Tg i +···W n / Tg n (1) In the formula, Tg(K) is the Tg of the copolymer, and Tg i (K) is the Tg of the homopolymer of monomer i, and W i is the mass fraction of each monomer. In this embodiment, the glass transition temperature Tg of the particulate polymer is a value measured by the method using DSC.

[0056] From the viewpoint of adhesion between the separator and the electrode and prevention of the particulate polymer from falling off from the coating layer, the average particle diameter of the particulate polymer is preferably 0.5 to 5 times the thickness of the coating layer, more preferably 1 to 2 times, even more preferably 1.1 to less than 1.5 times, and particularly preferably 1.2 to 1.4 times. The "average particle diameter" of the particulate polymer means the volume average particle diameter measured by the measurement method described in the examples. The "primary particle" of the particulate polymer means an independent particle that is united by a covalent bond. On the other hand, a form in which two or more primary particles are in contact with each other to form an aggregate is called a "secondary particle."

[0057] The particle size distribution MV / MN of the particulate polymer, which is obtained by dividing the volume average particle size MV of the particulate polymer by the number average particle size MN, is preferably 1.60 or less, more preferably 1.30 or less, even more preferably 1.20 or less, even more preferably 1.10 or less, and particularly preferably less than 1.10. The particle size distribution of the particulate polymer within the above range is preferable from the viewpoints of ensuring the uniformity of the thickness of the coating layer, improving cycle characteristics, and improving adhesion to the electrode, reducing the amount of particulate polymer on the small particle size side of the distribution embedded in the coating layer, improving adhesion to the electrode, and improving heat resistance, and reducing the total thickness of the separator. The lower limit of the particle size distribution MV / MN of the particulate polymer is not particularly limited, but may be 1.01 or more, or 1.01.

[0058] The particulate polymer contained in the coating layer is preferably in the form of primary particles. The average particle size of the primary particles of the particulate polymer is preferably 1 μm or more and 10 μm or less, more preferably 1 μm or more and 5 μm or less, and even more preferably 2 μm or more and 4 μm or less. The particulate polymer being in the form of primary particles means that the particulate polymer is uniformly dispersed in the coating layer, which improves the 180° peel strength, increases the adhesive strength with the electrode, suppresses thermal shrinkage, and ensures the uniformity of the thickness of the coating layer. When the average particle size of the primary particles is 1 μm or more and 10 μm or less, the particulate polymer is likely to form a structure protruding from the surface of the coating layer, which increases the adhesive strength with the electrode and suppresses thermal shrinkage.

[0059] Examples of the thermoplastic polymer include a (meth)acrylic polymer, a conjugated diene polymer, a polyvinyl alcohol resin, and a fluorine-containing resin.

[0060] From the viewpoint of high adhesion to the electrode and low thermal shrinkage, the thermoplastic polymer more preferably contains a (meth)acrylic polymer. The term "(meth)acrylic polymer" refers to a polymer or copolymer containing at least one (meth)acrylic compound selected from the group consisting of acrylic acid, methacrylic acid, acrylic acid esters, and methacrylic acid esters as a monomer. Such a (meth)acrylic compound can be represented by the following general formula: CH2=CR Y1 -COO-R Y2 In the formula, R Y1 represents a hydrogen atom or a methyl group, R Y2 R represents a hydrogen atom or a monovalent hydrocarbon group. Y2 When is a monovalent hydrocarbon group, it may have a substituent or a heteroatom. Examples of the monovalent hydrocarbon group include linear or branched chain alkyl groups, cycloalkyl groups, and aryl groups. Examples of the substituent include hydroxyl groups and phenyl groups, and examples of the heteroatom include halogen atoms and oxygen atoms. The (meth)acrylic compounds are used alone or in combination of two or more. Examples of the (meth)acrylic compounds include (meth)acrylic acid, linear alkyl (meth)acrylates, cycloalkyl (meth)acrylates, (meth)acrylates having a hydroxyl group, and (meth)acrylic acid aryl esters.

[0061] More specifically, the chain alkyl (meth)acrylate may include (meth)acrylates having a chain alkyl group having 1 to 3 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, and an isopropyl group; an n-butyl group, an isobutyl group, a t-butyl group, an n-hexyl group, a 2-ethylhexyl group; and a chain alkyl group having 4 or more carbon atoms, such as a lauryl group. An example of the (meth)acrylic acid aryl ester is phenyl (meth)acrylate.

[0062] Specific examples of the (meth)acrylate include (meth)acrylates having a chain alkyl group such as methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, butyl acrylate, isobutyl acrylate, t-butyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, lauryl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, butyl methacrylate, isobutyl methacrylate, t-butyl methacrylate, n-hexyl methacrylate, 2-ethylhexyl methacrylate, and lauryl methacrylate; and (meth)acrylates having an aromatic ring such as phenyl (meth)acrylate and benzyl (meth)acrylate.

[0063] Conjugated diene polymers are preferred because they have a conjugated diene compound as a monomer unit and are compatible with electrodes. Examples of conjugated diene compounds include 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, substituted linear conjugated pentadiene, substituted, and side-chain conjugated hexadienes, which may be used alone or in combination of two or more. Among these, 1,3-butadiene is particularly preferred. Conjugated diene polymers may contain a (meth)acrylic compound or other monomer as a monomer unit, as described below. Examples of such monomers include styrene-butadiene copolymers and their hydrogenated products, acrylonitrile-butadiene copolymers and their hydrogenated products, and acrylonitrile-butadiene-styrene copolymers and their hydrogenated products.

[0064] Examples of polyvinyl alcohol-based resins include polyvinyl alcohol and polyvinyl acetate.

[0065] Fluorine-containing resins are preferred from the viewpoint of voltage resistance, and examples thereof include polyvinylidene fluoride, polytetrafluoroethylene, and copolymers containing fluorine atoms, such as vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer, and ethylene-tetrafluoroethylene copolymer. The fluorine-containing resin is preferably a copolymer containing fluorine atoms.

[0066] Among the thermoplastic polymers listed above, the particulate polymer preferably contains at least one selected from the group consisting of copolymers containing (meth)acrylate as a monomer, styrene-butadiene copolymers, and copolymers containing fluorine atoms. The copolymers containing (meth)acrylate as a monomer preferably contain copolymers containing (meth)acrylic acid, butyl (meth)acrylate, and ethylhexyl (meth)acrylate as monomers. By including these specific thermoplastic polymers in the particulate polymer, it is possible to provide a separator for an electricity storage device that has higher adhesion to electrodes and a smaller thermal shrinkage rate.

[0067] The particulate polymer preferably contains a crosslinkable monomer. The crosslinkable monomer is not particularly limited, but may be, for example, a monomer having two or more radical polymerizable double bonds, or a monomer having a functional group that gives a self-crosslinking structure during or after polymerization. These may be used alone or in combination of two or more.

[0068] Examples of monomers having two or more radically polymerizable double bonds include divinylbenzene and polyfunctional (meth)acrylates, and polyfunctional (meth)acrylates are preferred. The polyfunctional (meth)acrylate may be at least one selected from the group consisting of bifunctional (meth)acrylates, trifunctional (meth)acrylates, and tetrafunctional (meth)acrylates. Specific examples include polyoxyethylene diacrylate, polyoxyethylene dimethacrylate, polyoxypropylene diacrylate, polyoxypropylene dimethacrylate, neopentyl glycol diacrylate, neopentyl glycol dimethacrylate, butanediol diacrylate, butanediol dimethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetraacrylate, and pentaerythritol tetramethacrylate. These may be used alone or in combination of two or more. Among these, from the same viewpoint as above, at least one of trimethylolpropane triacrylate and trimethylolpropane trimethacrylate is preferred.

[0069] (Resin binder) The coating layer preferably contains a resin binder for binding the inorganic fillers together and the inorganic filler and the base material. The type of resin for the resin binder is not particularly limited, but any resin that is insoluble in the electrolyte of a power storage device such as a lithium ion secondary battery and is electrochemically stable within the range of use of the power storage device such as a lithium ion secondary battery can be used.

[0070] Specific examples of the resin of the resin binder include polyolefins such as polyethylene and polypropylene; fluorine-containing resins such as polyvinylidene fluoride and polytetrafluoroethylene; fluorine-containing rubbers such as vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer and ethylene-tetrafluoroethylene copolymer; styrene-butadiene copolymers and their hydrogenated products, acrylonitrile-butadiene copolymers and their hydrogenated products, acrylonitrile-butadiene-styrene copolymers and their hydrogenated products, methacrylate-acrylate copolymers, styrene ... Examples of the resins include rubbers such as ethylene-acrylate copolymers, acrylonitrile-acrylate copolymers, ethylene propylene rubbers, polyvinyl alcohol, and polyvinyl acetate; cellulose derivatives such as ethyl cellulose, methyl cellulose, hydroxyethyl cellulose, and carboxymethyl cellulose; and resins having a melting point of 180° C. or higher, or resins having no melting point but a decomposition temperature of 200° C. or higher, such as polyphenylene ether, polysulfone, polyethersulfone, polyphenylene sulfide, polyetherimide, polyamideimide, polyamide, and polyester. These may be used alone or in combination of two or more.

[0071] The resin binder may include, for example, a resin latex binder. For example, a copolymer of an unsaturated carboxylic acid monomer and another monomer copolymerizable therewith may be used as the resin latex binder. Here, examples of the aliphatic conjugated diene monomer include butadiene and isoprene, examples of the unsaturated carboxylic acid monomer include (meth)acrylic acid, and examples of the other monomer include styrene. There is no particular restriction on the polymerization method of such a copolymer, but emulsion polymerization is preferred. There is no particular restriction on the emulsion polymerization method, and known methods can be used. There is no particular restriction on the method of adding the monomer and other components, and any of a lump-sum addition method, a divided addition method, and a continuous addition method can be used, and any of a single-stage polymerization method, a two-stage polymerization method, and a multi-stage polymerization method of three or more stages can be used as the polymerization method.

[0072] Specific examples of the resin binder include the following 1) to 7). 1) Polyolefins, such as polyethylene, polypropylene, ethylene propylene rubber, and modified products thereof; 2) Conjugated diene polymers, for example, styrene-butadiene copolymers and their hydrogenated products, acrylonitrile-butadiene copolymers and their hydrogenated products, acrylonitrile-butadiene-styrene copolymers and their hydrogenated products; 3) Acrylic polymers, such as methacrylate-acrylate copolymers, styrene-acrylate copolymers, and acrylonitrile-acrylate copolymers; 4) Polyvinyl alcohol-based resins, such as polyvinyl alcohol and polyvinyl acetate; 5) Fluorine-containing resins, such as polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymers, and ethylene-tetrafluoroethylene copolymers; 6) Cellulose derivatives, such as ethyl cellulose, methyl cellulose, hydroxyethyl cellulose, and carboxymethyl cellulose; and 7) Resins having a melting point and / or glass transition temperature of 180°C or higher, or polymers having no melting point but a decomposition temperature of 200°C or higher, such as polyphenylene ether, polysulfone, polyethersulfone, polyphenylene sulfide, polyetherimide, polyamideimide, polyamide, and polyester.

[0073] When the resin binder is a resin latex binder, its volume average particle diameter (D50) may be, for example, 50 nm to 500 nm, 60 nm to 460 nm, or 80 nm to 250 nm. The volume average particle diameter of the resin binder can be controlled, for example, by adjusting the polymerization time, polymerization temperature, raw material composition ratio, raw material charging order, pH, etc.

[0074] From the viewpoint of improving the 180° peel strength, the resin binder preferably has a glass transition temperature of 25° C. or lower, more preferably 10° C. or lower, and further preferably −15° C. or lower. From the viewpoint of transparency, the glass transition temperature is preferably −60° C. or higher.

[0075] From the viewpoint of improving the 180° peel strength, the volume average particle diameter (D50) of the resin binder is preferably 1 or more times the average pore diameter of the polyolefin microporous film, more preferably 2 or more times, and even more preferably 2.5 or more times. By selecting the volume average particle diameter (D50) of the resin binder in this manner, it is possible to hold the resin binder on the surface of the polyolefin microporous film, and the 180° peel strength is improved. From the viewpoint of improving the rate characteristics, the volume average particle diameter (D50) of the resin binder is preferably 10 or less times the average pore diameter of the polyolefin microporous film. The content ratio of the resin binder in the coating layer may be, for example, more than 0 parts by mass and 80 parts by mass or less, 1 part by mass or more and 20 parts by mass or less, 2 parts by mass or more and 10 parts by mass or less, or 3 parts by mass or more and 5 parts by mass or less, based on the total amount of the coating layer.

[0076] From the viewpoints of wettability to the substrate, binding between the substrate and the particulate polymer, binding between the coating layer and the particulate polymer, binding between the substrate and the coating layer, and adhesion to the electrode, the Tg of the resin binder is preferably less than 40° C. From the viewpoint of ion permeability, the Tg of the resin binder is more preferably −100° C. or higher, even more preferably −50° C. or higher, and particularly preferably −40° C. or higher, and from the viewpoint of binding between the substrate and the particulate polymer, it is more preferably less than 20° C., even more preferably less than 15° C., and particularly preferably less than 0° C.

[0077] (Water-soluble polymer) The coating layer may further contain a water-soluble polymer in addition to the inorganic filler and the particulate polymer. The water-soluble polymer may be incompatible with the thermoplastic polymer of the particulate polymer. In general, the water-soluble polymer functions as a dispersant in the coating liquid for forming the coating layer containing the inorganic filler and the particulate polymer of the thermoplastic polymer, and functions as a dispersant and / or a water retention agent when the coating liquid is a water-based paint.

[0078] The content of the water-soluble polymer in the coating layer is preferably 0.04 parts by mass or more and less than 2 parts by mass, more preferably 0.04 parts by mass or more and 1.5 parts by mass or less, and even more preferably 0.1 parts by mass or more and 1 part by mass or less, relative to 100 parts by mass of the inorganic filler. When the content of the water-soluble polymer is 0.04 parts by mass or more, the binding property between the inorganic components is improved, and thermal shrinkage can be further suppressed. In addition, the precipitation of the components during the preparation of the slurry of the coating layer can be suppressed, and the components can be dispersed stably. When the content of the water-soluble polymer is 5 parts by mass or less, streaks and unevenness during the formation of the coating layer can be suppressed.

[0079] The water-soluble polymer also contributes to the binding between inorganic fillers in the coating layer. From the viewpoint of suppressing the thermal shrinkage of the separator, the water-soluble polymer preferably has a weight loss rate of less than 10% at 150°C, where the weight at 50°C in thermogravimetry is taken as 100%.

[0080] The water-soluble polymer may be a polymer derived from a natural product, a synthetic product, a semi-synthetic product, etc., but from the viewpoint of forming a paint from inorganic components and organic components, particularly a water-based paint, it is preferable that the water-soluble polymer is an anionic, cationic, amphoteric, or nonionic polymer, and more preferably an anionic, cationic, or amphoteric polymer.

[0081] Examples of anionic polymers include modified starches such as carboxymethyl starch and starch phosphate; anionic cellulose derivatives such as carboxymethyl cellulose; ammonium salts or alkali metal salts of polyacrylic acid; gum arabic; carrageenan; sodium chondroitin sulfate; sulfonic acid compounds such as sodium polystyrene sulfonate, sodium polyisobutylene sulfonate, and naphthalene sulfonic acid condensate salt; and polyethyleneimine xanthate salt. Among these, from the viewpoint of achieving an appropriate balance between rigidity, rate characteristics, and cycle characteristics of the power storage device, anionic polymers containing metal salts as counter cations are preferred; anionic cellulose derivatives and ammonium salts or alkali metal salts of polyacrylic acid are also preferred; from the viewpoint of the balance between heat resistance and rate characteristics, alkali metal salts of polyacrylic acid are more preferred, and sodium polyacrylate is even more preferred.

[0082] Ammonium salts or alkali metal salts of polyacrylic acid are -COO - It refers to a polymer in which at least one of the moieties forms a salt with an ammonium ion or an alkali metal ion. Examples of alkali metal ions include sodium ions (Na + ), potassium ion (K + ) etc.

[0083] The ammonium salt or alkali metal salt of polyacrylic acid may be at least one of the following (I) to (III): (I) A monomer having one ammonium salt or alkali metal salt of a carboxylic acid (C i ) or a homopolymer of multiple monomers (C i ) and copolymers with other monomers; (II) Monomers having a plurality of ammonium salts or alkali metal salts of carboxylic acids (C ii ) homopolymer or monomer (C ii ) and other monomers; and (III) Ammonium salts or alkali metal salts of polymers or copolymers obtained by polymerizing or copolymerizing monomers having one or more carboxylic acids.

[0084] Monomers having one ammonium salt or alkali metal salt of a carboxylic acid (C i ) include, for example, sodium (meth)acrylate and ammonium (meth)acrylate.

[0085] Monomers having multiple ammonium salts or alkali metal salts of carboxylic acids (C ii Examples of the acryloyloxy group include ammonium salts or sodium salts of 11-(methacryloyloxy)undecane-1,1-dicarboxylic acid; ammonium salts, monosodium salts, or disodium salts of ethylenically unsaturated dicarboxylic acids such as fumaric acid, maleic acid, itaconic acid, and citraconic acid; and alicyclic polycarboxylic acids having a (meth)acryloyl group.

[0086] Monomer (C i ) or monomer (C ii Examples of monomers copolymerizable with methyl ethylenically unsaturated dicarboxylic acids include (meth)acrylamide; ethylenically unsaturated dicarboxylic acids such as fumaric acid, maleic acid, itaconic acid, and citraconic acid; and ethylenically unsaturated dicarboxylic acid anhydrides such as maleic anhydride, itaconic anhydride, and citraconic anhydride.

[0087] Examples of the ammonium salt or alkali metal salt of a polymer or copolymer obtained by polymerizing or copolymerizing a monomer having one or more carboxylic acids include sodium polyacrylate and ammonium polyacrylate.

[0088] The structures of the ammonium salts or alkali metal salts of polyacrylic acid explained above in (I) to (III) may overlap with each other.

[0089] The ammonium salt or alkali metal salt of polyacrylic acid described above in (I) to (III) preferably has a small content of polyvalent cations when dissolved in water. Examples of polyvalent cations include magnesium ions, calcium ions, and iron ions. By reducing the content of these ions, the dispersibility of the particulate polymer in the mixed slurry with the particulate polymer is stabilized.

[0090] Examples of cationic polymers include cationic starch; chitosan; gelatin; homopolymers or copolymers of dimethylaminoethyl (meth)acrylate quaternary salts; homopolymers or copolymers of dimethylallylammonium chloride; polyamidines and their copolymers; polyvinylimidazolines; dicyandiamide condensates; epichlorohydrin-dimethylamine condensates; and polyethyleneimines.

[0091] Examples of the amphoteric polymer include dimethylaminoethyl (meth)acrylate quaternary salt-acrylic acid copolymer, Hofmann degradation products of polyacrylamide, and the like.

[0092] Examples of nonionic polymers include starch and its derivatives; cellulose derivatives such as methyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose, and their ammonium salts or alkali metal salts; gums such as guar gum and their modifications; and synthetic polymers and their modifications, such as polyvinyl alcohol, polyacrylamide, polyethylene glycol, polymethyl vinyl ether, polyisopropylacrylamide, and copolymers of vinyl alcohol and other monomers.

[0093] The water-soluble polymer may or may not have an amide bond-containing cyclic structure.

[0094] The water-soluble polymer having an amide bond-containing cyclic structure refers to a homopolymer or copolymer having a group having an amide bond-containing cyclic structure and a skeleton derived from a polymerizable double bond. The water-soluble polymer having an amide bond-containing cyclic structure may have one or more amide bond-containing cyclic structures.

[0095] The group having an amide bond-containing cyclic structure includes the following formula (2): [ka] Specific examples of the water-soluble polymer having an amide bond-containing cyclic structure include homopolymers of monomers having a group having an amide bond-containing cyclic structure and a polymerizable double bond, such as poly(N-vinylcaprolactam) which is a homopolymer of N-vinylcaprolactam, and polyvinylpyrrolidone (PVP) which is a homopolymer of vinylpyrrolidone; copolymers of two or more monomers having a group having an amide bond-containing cyclic structure and a polymerizable double bond (N-vinylcaprolactam, vinylpyrrolidone, etc.); and copolymers of one or more monomers having a group having an amide bond-containing cyclic structure and a polymerizable double bond (N-vinylcaprolactam, vinylpyrrolidone, etc.) with one or more monomers having another polymerizable double bond (monomers other than the monomer having a group having an amide bond-containing cyclic structure and a polymerizable double bond).

[0096] Examples of monomers copolymerizable with the monomer having a group having an amide bond-containing cyclic structure and a polymerizable double bond include vinyl non-cyclic amides; (meth)acrylic acid and esters thereof; (meth)acrylamide and derivatives thereof; styrene and derivatives thereof; vinyl esters such as vinyl acetate; α-olefins; basic unsaturated compounds such as vinylimidazole and vinylpyridine and derivatives thereof; carboxyl group-containing unsaturated compounds and acid anhydrides thereof; vinyl sulfonic acid and derivatives thereof; vinyl ethylene carbonate and derivatives thereof; and vinyl ethers.

[0097] (Additives) The coating layer may consist of only inorganic filler, particulate polymer and any water-soluble polymer, or may further contain additives other than these. Examples of additives include low molecular weight dispersants other than water-soluble polymers; thickeners; antifoaming agents; and pH adjusters such as ammonium hydroxide. Specific examples of low molecular weight dispersants include monomers (C ii ), and non-polymerizable compounds having a plurality of ammonium salts or alkali metal salts of carboxylic acids (for example, sodium alginate and sodium hyaluronate).

[0098] Specific examples of the defoaming agent include those represented by the following formula (A): [ka] {where, R 5 ~R 8 each independently represents an alkyl group having 1 to 10 carbon atoms, and n and m each independently represent an integer of 0 or more, provided that n+m=0 to 40.} It is preferable to use a surfactant (acetylene-based surfactant) containing an ethoxylated product of acetylene glycol represented by the following formula: Specific examples of the alkyl group having 1 to 10 carbon atoms may be linear, branched, or cyclic, and include, for example, a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an n-hexyl group, an n-heptyl group, an n-octyl group, an n-nonyl group, and an n-decyl group.

[0099] Specific examples of the acetylene glycol represented by formula (A) include 2,5,8,11-tetramethyl-6-dodecyne-5,8-diol, 5,8-dimethyl-6-dodecyne-5,8-diol, 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 4,7-dimethyl-5-decyne-4,7-diol, 2,3,6,7-tetramethyl-4-octyne-3,6-diol, 3,6-dimethyl-4-octyne-3,6-diol, 2,5-dimethyl-3-hexyne-2,5-diol, an ethoxylated 2,4,7,9-tetramethyl-5-decyne-4,7-diol (ethylene oxide addition mole number: 1.3), an ethoxylated 2,4,7,9-tetramethyl-5-decyne-4,7-diol (ethylene oxide addition mole number: 1.3), ethoxylated 3,6-dimethyl-4-octyne-3,6-diol (ethylene oxide added mole number: 4), ethoxylated 2,5,8,11-tetramethyl-6-dodecyne-5,8-diol (ethylene oxide added mole number: 6), ethoxylated 2,4,7,9-tetramethyl-5-decyne-4,7-diol (ethylene oxide added mole number: 10), ethoxylated 2,4,7,9-tetramethyl-5-decyne-4,7-diol (ethylene oxide added mole number: 30), ethoxylated 3,6-dimethyl-4-octyne-3,6-diol (ethylene oxide added mole number: 20), and the like. These may be used alone or in combination of two or more.

[0100] The acetylene-based surfactant can be obtained as a commercially available product. Examples of such commercially available products include Olfine SPC (manufactured by Nissin Chemical Industry Co., Ltd., active ingredient 80 parts by mass, pale yellow liquid), Olfine AF-103 (manufactured by Nissin Chemical Industry Co., Ltd., pale brown liquid), Olfine AF-104 (manufactured by Nissin Chemical Industry Co., Ltd., pale brown liquid), Olfine SK-14 (manufactured by Nissin Chemical Industry Co., Ltd., short yellow viscous liquid), Olfine AK-02 (manufactured by Nissin Chemical Industry Co., Ltd., short yellow viscous liquid), Olfine AF-201F (manufactured by Nissin Chemical Industry Co., Ltd., short yellow viscous liquid), Olfine D-10PG (manufactured by Nissin Chemical Industry Co., Ltd., active ingredient 50 parts by mass, pale yellow liquid), and Olfine E. -1004 (manufactured by Nissin Chemical Industry Co., Ltd., active ingredient 100 parts by mass, pale yellow liquid), Olfine E-1010 (manufactured by Nissin Chemical Industry Co., Ltd., active ingredient 100 parts by mass, pale yellow liquid), Olfine E-1020 (manufactured by Nissin Chemical Industry Co., Ltd., active ingredient 100 parts by mass, pale yellow liquid), Olfine E-1030W (manufactured by Nissin Chemical Industry Co., Ltd., active ingredient 75 parts by mass, pale yellow liquid), Surfynol 420 (manufactured by Nissin Chemical Industry Co., Ltd., active ingredient 100 parts by mass, pale yellow viscous body), Surfynol 440 (manufactured by Nissin Chemical Industry Co., Ltd., active ingredient 100 parts by mass, pale yellow viscous body), Surfynol 104E (manufactured by Nissin Chemical Industry Co., Ltd., active ingredient 50 parts by mass, pale yellow viscous body), and the like.

[0101] As the post-added surfactant, instead of or together with the acetylene surfactant, a polyether surfactant and / or a silicone surfactant can also be used. Representative examples of polyether surfactants include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polyoxyethylene oleyl ether, polyoxyethylene stearyl ether, polyoxyethylene lauryl ether, polyoxyethylene dodecyl ether, polyoxyethylene nonylphenyl ether, polyoxyethylene octylphenyl ether, and polyoxyethylene-polyoxypropylene block copolymers. Among these, polyethylene glycol is particularly preferred. These surfactants may be used alone or in combination of two or more.

[0102] The polyether surfactant can be obtained as a commercially available product, and examples of such commercially available products include E-D052, E-D054, and E-F010 (manufactured by San Nopco Ltd.).

[0103] The silicone surfactant may be linear, branched, or cyclic, as long as it contains at least a silicone chain, and may contain either a hydrophobic group or a hydrophilic group. Specific examples of the hydrophobic group include alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, and n-decyl; cyclic alkyl groups such as cyclohexyl; and aromatic hydrocarbon groups such as phenyl. Specific examples of the hydrophilic group include amino groups, thiol groups, hydroxyl groups, alkoxy groups, carboxylic acids, sulfonic acids, phosphoric acids, nitric acids, and their organic and inorganic salts, ester groups, aldehyde groups, glycerol groups, and heterocyclic groups. Representative examples of silicone surfactants include dimethyl silicone, methylphenyl silicone, chlorophenyl silicone, alkyl-modified silicone, fluorine-modified silicone, amino-modified silicone, alcohol-modified silicone, phenol-modified silicone, carboxy-modified silicone, epoxy-modified silicone, fatty acid ester-modified silicone, and polyether-modified silicone.

[0104] Silicone surfactants can be obtained as commercially available products. Examples of such commercially available products include BYK-300, BYK-301, BYK-302, BYK-306, BYK-307, BYK-310, BYK-313, BYK-320BYK-333, BYK-341, BYK-345, BYK-346, BYK-347, BYK-348, and BYK-349 (all trade names, manufactured by BYK Japan Co., Ltd.), KM-80, KF-351A, KF-352A, KF-353, KF-354L, KF-355A, KF-615A, KF-945, and KF-64. 0, KF-642, KF-643, KF-6020, X-22-4515, KF-6011, KF-6012, KF-6015, KF-6017 (all trade names, manufactured by Shin-Etsu Chemical Co., Ltd.), SH-28PA, SH8400, SH-190, SF-8428 (all trade names, manufactured by Dow Corning Toray Co., Ltd.), Polyflow KL-245, Polyflow KL-270, Polyflow KL-100 (all trade names, manufactured by Kyoeisha Chemical Co., Ltd.), Silface SAG002, Silface SAG005, Silface SAG0085 (all trade names, manufactured by Nissin Chemical Industry Co., Ltd.), and the like.

[0105] (Amount of coating layer) The amount of the coating layer relative to the substrate, i.e., the amount of the coating layer per unit area of ​​one surface of the substrate, is preferably 0.5 g / m by weight. 2 More preferably, 1.0 g / m 2 More than 0.15 cm 3 / m 2 More preferably, 0.30 cm 3 / m 2 The upper limit of the amount of the coating layer is preferably 10.0 g / m 2 Less than 7.0 g / m 2 The volume is 3.50 cm 3 / m 2 The volume is 2.50 cm 3 / m 2The amount of the coating layer is preferably equal to or more than the lower limit in terms of improving the adhesive strength between the coating layer and the electrode and suppressing thermal shrinkage, whereas the amount of the coating layer is preferably equal to or less than the upper limit in terms of suppressing a decrease in ion permeability.

[0106] (Coating layer thickness) The thickness of either one of the coating layers disposed on at least one of the substrates is preferably 0.3 μm or more and 5.0 μm or less, more preferably 0.5 μm or more and 2.5 μm or less, and even more preferably 0.7 μm or more and 1.3 μm or less. When the thickness of the coating layer is 0.3 μm or more, the thermal shrinkage rate can be further suppressed, and the adhesive force between the electrode and the substrate can be easily made uniform, and as a result, the characteristics of the electricity storage device can be improved. When the thickness of the coating layer is 1.3 μm or less, it is preferable in that the decrease in ion permeability can be suppressed and a thin separator for an electricity storage device can be obtained. That is, by reducing the thickness of the separator, an electricity storage device with a large capacity per volume can be manufactured. On the other hand, from the viewpoint of preventing the particulate polymer from slipping off the coating layer, it is preferable that the thickness is 1.6 μm or more or 2.1 μm or more. The thickness of the coating layer can be adjusted, for example, by changing the type or concentration of the particulate polymer in the coating liquid applied to the substrate, the amount of the coating liquid applied, the coating method, the coating conditions, and the like. However, the method of adjusting the thickness of the coating layer is not limited thereto.

[0107] Fig. 1 is a schematic diagram of the surface of the coating layer of the separator for an electricity storage device of this embodiment. As shown in Fig. 1, inorganic filler (1) and particulate polymer (2) of a thermoplastic polymer protruding from the coating layer are present on the surface of the coating layer (10). In Fig. 1, the particulate polymer is present in the form of primary particles without agglomerating with other particulate polymers.

[0108] Fig. 2 is a cross-sectional view taken along the line AA of the separator for a power storage device in Fig. 1. As shown in Fig. 2, the coating layer (20) is formed in an inclined shape so that it becomes continuously thicker from an inorganic filler portion that is 1.5D or more away from the volume center of each particulate polymer in the horizontal direction (the surface direction of the coating layer) toward the protruding particulate polymer (2). The inclination of the inclined coating layer becomes gentler as it moves away from the protruding particulate polymer and becomes steeper as it approaches the protruding particulate polymer. The inorganic filler (1) covers a part of the periphery of the protruding portion so as to ride along the contour of the particulate polymer, and the vicinity of the center of the protruding portion is exposed on the surface of the coating layer.

[0109] <<Method for producing separator for power storage device>> <Method of Manufacturing Substrate> The method for producing the substrate is not particularly limited, and can adopt a known production method, for example, can adopt either wet porosity method or dry porosity method.Examples of wet porosity method include, for example, when the substrate is a polyolefin microporous film, the method of melt-kneading a polyolefin resin composition with a plasticizer, forming it into a sheet, and optionally stretching it, and then extracting the plasticizer to make it porous; the method of melt-kneading a polyolefin resin composition containing a polyolefin resin as a main component, extruding it at a high draw ratio, and then peeling the polyolefin crystal interface by heat treatment and stretching it to make it porous; the method of melt-kneading a polyolefin resin composition with an inorganic filler, forming it into a sheet, and then peeling the interface between the polyolefin and the inorganic filler by stretching it to make it porous; and the method of dissolving the polyolefin resin composition, immersing it in a poor solvent for polyolefin, solidifying the polyolefin, and simultaneously removing the solvent to make it porous.

[0110] The method for producing the substrate may be a known method, such as a chemical bonding method in which a web is immersed in a binder and dried to bond the fibers together, a thermal bonding method in which heat-melting fibers are mixed into the web and the fibers are partially melted to bond the fibers together, a needle punch method in which a needle having a barb is repeatedly pierced into the web to mechanically entangle the fibers, and a hydroentanglement method in which a high-pressure water stream is sprayed from a nozzle through a net (screen) onto the web to entangle the fibers.

[0111] Hereinafter, as an example of a method for producing a polyolefin microporous membrane, a method of melt-kneading a polyolefin resin composition and a plasticizer, forming the composition into a sheet, and then extracting the plasticizer will be described. A polyolefin resin composition and a plasticizer are melt-kneaded. As a melt-kneading method, for example, a method of feeding a polyolefin resin and other additives as necessary into a resin kneading device such as an extruder, a kneader, a lab plastomill, a kneading roll, and a Banbury mixer, and introducing and kneading a plasticizer at an arbitrary ratio while heating and melting the resin components. In this case, it is preferable to pre-knead the polyolefin resin, other additives, and the plasticizer in a predetermined ratio using a Henschel mixer or the like before feeding them into the resin kneading device. More preferably, only a part of the plasticizer is fed in the pre-kneading, and the remaining plasticizer is kneaded while being side-fed into the resin kneading device.

[0112] As the plasticizer, a non-volatile solvent capable of forming a homogeneous solution at or above the melting point of the polyolefin can be used. Examples of the plasticizer include hydrocarbons such as liquid paraffin and paraffin wax; esters such as dioctyl phthalate and dibutyl phthalate; and higher alcohols such as oleyl alcohol and stearyl alcohol. Among these, liquid paraffin is preferred.

[0113] The ratio of the polyolefin resin composition and the plasticizer is not particularly limited as long as they can be uniformly melt-kneaded and molded into a sheet. For example, the mass fraction of the plasticizer in the composition consisting of the polyolefin resin composition and the plasticizer is preferably 30 parts by mass or more and 80 parts by mass or less, more preferably 40 parts by mass or more and 70 parts by mass or less. By setting the mass fraction of the plasticizer in this range, it is preferable to achieve both the melt tension during melt molding and the formability of a uniform and fine pore structure.

[0114] The molten kneaded product obtained by heating, melting, and kneading as described above is molded into a sheet. As a method for producing a sheet-shaped molded product, for example, the molten kneaded product is extruded into a sheet through a T-die or the like, and is brought into contact with a thermal conductor to a temperature sufficiently lower than the crystallization temperature of the resin component to solidify. Examples of thermal conductors used for cooling and solidifying include metal, water, air, and plasticizer itself, but metal rolls are preferred because of their high thermal conductivity. In this case, when the molten kneaded product is brought into contact with the metal rolls, it is more preferred to sandwich the molten kneaded product between the rolls, as this further increases the efficiency of thermal conduction, orients the sheet, increases the film strength, and improves the surface smoothness of the sheet. When extruding the molten kneaded product into a sheet from a T-die, the die lip interval is preferably 400 μm or more and 3000 μm or less, and more preferably 500 μm or more and 2500 μm or less.

[0115] The sheet-like molded product thus obtained is then preferably stretched. As the stretching process, either uniaxial stretching or biaxial stretching can be suitably used. Biaxial stretching is preferred from the viewpoint of the strength of the resulting microporous film. When the sheet-like molded product is stretched in the biaxial direction at a high ratio, the molecules are oriented in the planar direction, and the finally obtained porous substrate is less likely to tear and has high pin puncture strength. Examples of the stretching method include simultaneous biaxial stretching, sequential biaxial stretching, multi-stage stretching, and multiple stretching. Simultaneous biaxial stretching is preferred from the viewpoints of improving pin puncture strength, uniformity of stretching, and shutdown property.

[0116] The stretching ratio is preferably in the range of 20 times to 100 times in terms of areal ratio, and more preferably in the range of 25 times to 50 times. The stretching ratio in each axial direction is preferably in the range of 4 times to 10 times in the MD direction and 4 times to 10 times in the TD direction, and more preferably in the range of 5 times to 8 times in the MD direction and 5 times to 8 times in the TD direction. By setting the stretching ratio within this range, it is possible to impart more sufficient strength, and it is preferable in that it prevents membrane breakage in the stretching process and obtains high productivity. In addition, the MD direction means, for example, the machine direction when the polyolefin microporous membrane is continuously molded, and the TD direction means the direction crossing the MD direction at an angle of 90°.

[0117] The sheet-like molded product obtained as described above may be further rolled. The rolling can be performed, for example, by a pressing method using a double belt press or the like. The rolling can increase the orientation of the surface layer of the sheet-like molded product in particular. The rolling area ratio is preferably more than 1 and less than 3 times, and more preferably more than 1 and less than 2 times. By setting the rolling ratio within this range, the film strength of the finally obtained porous substrate is increased, and a more uniform porous structure can be formed in the thickness direction of the film, which is preferable.

[0118] Next, the plasticizer is removed from the sheet-shaped molded body to obtain a porous substrate. For example, a method of removing the plasticizer includes immersing the sheet-shaped molded body in an extraction solvent to extract the plasticizer and drying it thoroughly. The method of extracting the plasticizer may be either a batch method or a continuous method. In order to suppress the shrinkage of the porous substrate, it is preferable to restrain the end of the sheet-shaped molded body during a series of steps of immersion and drying. The removal of the plasticizer is preferably controlled so that the amount of the plasticizer is preferably 0.1 parts by mass or more and 1.6 parts by mass or less, more preferably 0.2 parts by mass or more and 1.2 parts by mass or less, and 0.3 parts by mass or more and 1.0 parts by mass or less, based on the total mass of the substrate obtained. By the amount of the plasticizer being within the above range, the internal resistance of the battery can be reduced while improving the binding strength between the substrate and the coating layer.

[0119] As the extraction solvent, it is preferable to use one that is a poor solvent for polyolefin resins and a good solvent for plasticizers, and has a boiling point lower than the melting point of polyolefin resins. Examples of such extraction solvents include hydrocarbons such as n-hexane and cyclohexane; halogenated hydrocarbons such as methylene chloride and 1,1,1-trichloroethane; non-chlorine halogenated solvents such as hydrofluoroethers and hydrofluorocarbons; alcohols such as ethanol and isopropanol; ethers such as diethyl ether and tetrahydrofuran; and ketones such as acetone and methyl ethyl ketone. These extraction solvents may be recovered and reused by operations such as distillation.

[0120] In order to suppress shrinkage of the porous substrate, a heat treatment such as heat fixing or heat relaxation may be performed after the stretching step or after the formation of the porous substrate. The porous substrate may be subjected to post-treatment such as hydrophilization treatment with a surfactant or crosslinking treatment with ionizing radiation or the like.

[0121] Here is an example of a dry porosity method, which is different from the above wet porosity method. First, a film is produced by directly stretching and oriented after melt kneading in an extruder without using a solvent, and then a microporous film is produced by sequentially going through an annealing process, a cold stretching process, and a hot stretching process. Examples of the dry porosity method include a method in which a molten resin is stretched and oriented through a T-die from an extruder, and an inflation method, and the method is not particularly limited.

[0122] <Method of Arranging the Covering Layer> A coating layer is disposed on at least one surface of the substrate produced as described above. The method for disposing the coating layer is not particularly limited, and examples thereof include a method of applying a coating liquid containing an inorganic filler and a particulate polymer to the substrate.

[0123] As the coating liquid, a dispersion in which an inorganic filler and a particulate polymer are dispersed in a solvent or dispersion medium (hereinafter simply referred to as "medium") that does not dissolve the particulate polymer can be used. Preferably, the particulate polymer is synthesized by emulsion polymerization, and the emulsion obtained by the emulsion polymerization can be used as it is as the coating liquid.

[0124] The medium of the coating liquid is preferably one that can uniformly and stably disperse or dissolve the inorganic filler, the particulate polymer, and optionally the water-soluble polymer, and examples thereof include N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, water, ethanol, methanol, toluene, hot xylene, methylene chloride, and hexane. Preferably, the medium of the coating liquid is water, or a mixed medium consisting of water and a water-soluble organic medium. Examples of the water-soluble organic medium include, but are not limited to, ethanol and methanol. Among these, water is more preferable. When the coating liquid is applied to the substrate, if the coating liquid penetrates into the substrate, the particulate polymer containing the polymer will block the surface and the inside of the pores of the substrate, and the permeability will be easily reduced. In this regard, in the case of an aqueous dispersion using water as the medium of the coating liquid, the coating liquid will not easily penetrate into the substrate, and the particulate polymer containing the polymer will easily be present mainly on the outer surface of the substrate, so that the reduction in permeability can be more effectively suppressed, which is preferable.

[0125] The coating liquid may contain various additives such as a dispersant such as a surfactant; a thickener; a wetting agent; a defoaming agent; and a pH adjuster including an acid or an alkali.

[0126] Examples of a method for dispersing or dissolving the inorganic filler, the particulate polymer, and, if necessary, the water-soluble polymer in the medium of the coating liquid include a ball mill, a bead mill, a planetary ball mill, a vibrating ball mill, a sand mill, a colloid mill, an attritor, a roll mill, high-speed impeller dispersion, a disperser, a homogenizer, a high-speed impact mill, ultrasonic dispersion, and mechanical stirring with a stirring blade or the like.

[0127] The procedure for preparing the coating liquid is preferably as follows: first, add the water-soluble polymer to the coating liquid in which the inorganic filler is dispersed, and then add the resin binder and the particulate polymer. By preparing the coating liquid in this order, the water-soluble polymer adsorbs and protects the metal ions contained in the inorganic filler, and the aggregation of the resin binder and the particulate polymer can be prevented.

[0128] The viscosity of the coating liquid is preferably 20 mPa·s or more and 80 mPa·s or less, more preferably 60 mPa·s or less, and even more preferably 40 mPa·s or less. A viscosity of 20 mPa·s or more and 80 mPa·s or less is preferable from the viewpoint of accelerating the settling of the particulate polymer and increasing the gradient rate of the coating layer and increasing the contact rate between the particulate polymer and the substrate surface in the process of forming a coating layer by removing the solvent from the coating film after coating.

[0129] Before coating, the substrate may be surface-treated. Surface treatment is preferable because it makes it easier to apply the coating liquid, improves adhesion between the substrate and the thermoplastic polymer, and makes it easier to control the 180° peel strength to 200 gf / cm or more. Examples of the surface treatment method include corona discharge treatment, plasma treatment, mechanical roughening, solvent treatment, acid treatment, and ultraviolet oxidation. Examples of the surface treatment include corona discharge treatment.

[0130] The method of applying the coating liquid onto the substrate is not particularly limited as long as it can realize the desired coating pattern, coating film thickness, and coating area. For example, gravure coater method, small diameter gravure coater method, reverse roll coater method, transfer roll coater method, kiss coater method, dip coater method, knife coater method, air doctor coater method, blade coater method, rod coater method, squeeze coater method, cast coater method, die coater method, screen printing method, spray coating method, inkjet coating method, etc. can be mentioned. Among these, gravure coater method or spray coating method is preferred from the viewpoint of high freedom of coating shape of particulate polymer and easy obtaining of preferred area ratio.

[0131] The coating method is preferably a gravure coater method or the like, in which the coating is applied at a high shear rate, and the shear rate is preferably 40,000 sec -1 More than 120,000sec -1 When the shear rate is within this range, the particulate polymer is well dispersed as primary particles, and it is easier to control the 180° peel strength to 200 gf / cm or more.

[0132] The method for removing the medium from the coating film after coating is not particularly limited as long as it does not adversely affect the substrate and the coating layer. For example, a method of drying the substrate at a temperature below its melting point while fixing the substrate, a method of drying under reduced pressure at a low temperature, a method of immersing the substrate in a medium that is a poor solvent for the particulate polymer to solidify the particulate polymer into particles and simultaneously extract the medium, etc. can be mentioned.

[0133] <Preparation of Separator Roll> The obtained separator for an electricity storage device is preferably wound into a wound body. By forming the separator into a wound body, it can be easily unwound at high speed, and the productivity in the production process of the electricity storage device can be increased.

[0134] <Electricity storage device> The electric storage device of the present embodiment includes the separator for the electric storage device of the present embodiment. The electric storage device is not particularly limited, but examples thereof include batteries such as non-aqueous electrolyte secondary batteries, condensers, and capacitors. Among them, in order to utilize the advantages of the separator for the electric storage device of the present embodiment, a battery is preferred, a non-aqueous electrolyte secondary battery is more preferred, and a lithium ion secondary battery is even more preferred. The lithium ion secondary battery has a positive electrode, a negative electrode, the separator for the electric storage device of the present embodiment disposed between the positive electrode and the negative electrode, and a non-aqueous electrolyte. The electric storage device of the present embodiment includes the separator for the electric storage device, and thus has excellent characteristics such as electric storage performance, and in the case of a lithium ion secondary battery, has excellent battery characteristics.

[0135] When the power storage device of the present embodiment is a lithium ion secondary battery, the positive electrode, the negative electrode, and the nonaqueous electrolyte are not limited, and known materials can be used. As the positive electrode, a positive electrode having a positive electrode active material layer containing a positive electrode active material formed on a positive electrode current collector can be suitably used. As the positive electrode current collector, for example, aluminum foil can be used. As the positive electrode active material, for example, lithium-containing composite oxides such as LiCoO2, LiNiO2, spinel type LiMnO4, and olivine type LiFePO4 can be used. In addition to the positive electrode active material, the positive electrode active material layer may appropriately contain a binder, a conductive material, and the like.

[0136] As the negative electrode, a negative electrode having a negative electrode active material layer containing a negative electrode active material formed on a negative electrode current collector can be suitably used. As the negative electrode current collector, for example, copper foil can be used. As the negative electrode active material, for example, carbon materials such as graphite, non-graphitizable carbon, graphitizable carbon, and composite carbon bodies; silicon, tin, metallic lithium, and various alloy materials can be used.

[0137] The non-aqueous electrolyte is not particularly limited, but an electrolyte solution obtained by dissolving an electrolyte in an organic solvent can be used. Examples of the organic solvent include propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. Examples of the electrolyte include lithium salts such as LiClO4, LiBF4, and LiPF6.

[0138] <<Method for manufacturing an electricity storage device>> The method for manufacturing an electricity storage device using the separator of this embodiment is not particularly limited. For example, the following method can be exemplified. First, the separator of this embodiment is manufactured by the above-mentioned method. The size and shape of the separator may be, for example, a vertically elongated shape with a width of 10 to 500 mm, preferably 80 to 500 mm, and a length of 200 to 10,000 m, preferably 1,000 to 6,000 m. Next, the positive electrode-separator-negative electrode-separator, or negative electrode-separator-positive electrode-separator, are laminated in this order, and wound into a circular or flat spiral shape to obtain a wound body. The wound body is stored in a device can (for example, a battery can), and an electrolyte solution is further injected to manufacture the device. Alternatively, the electrode and the separator may be folded to form a wound body, which is then placed in a device container (for example, an aluminum film) and the electrolyte solution is injected to manufacture the device.

[0139] At this time, the wound body can be pressed. Specifically, a method can be exemplified in which a separator, a current collector, and an electrode having an active material layer formed on at least one surface of the current collector are stacked such that the coating layer and the active material layer face each other, and then pressed.

[0140] The pressing temperature is set as T 1.00 It is preferable to carry out the reaction at a temperature of T 1.00 is the temperature at which the DDSC value is the minimum value between 0°C and 150°C when the heat flow difference per unit time measured by DSC (differential scanning calorimetry) is differentiated by temperature. 1.00By pressing at a temperature of 30° C. or higher, the coating layer is sufficiently deformed and good adhesive strength can be obtained. For example, 35° C. or higher is preferable. In order to suppress clogging of the pores in the separator or thermal shrinkage due to heat pressing, the pressing temperature is preferably lower than the melting point of the material contained in the base material, and more preferably 130° C. or lower. In order to suppress clogging of the pores in the separator, the pressing pressure is preferably 20 MPa or lower from the viewpoint of suppressing clogging of the pores in the separator. The pressing time may be 1 second or less when using a roll press, or may be a surface press for several hours, but is preferably 2 hours or less from the viewpoint of productivity. When the separator for an electric storage device of this embodiment is used and the above manufacturing process is performed, press back can be suppressed when the wound body consisting of the electrode and the separator is press-molded. Therefore, the yield reduction in the device assembly process can be suppressed and the production process time can be shortened.

[0141] In addition, the adhesiveness can be developed without pressing the wound body. Specifically, an example of the method is one in which the adhesiveness is developed between the coating layer of the separator and the opposing electrode by the pressure generated in the device can when the wound body is housed in a device can and an electrolyte is injected to manufacture an electricity storage device, or by the pressure caused by the expansion and contraction of the electrodes due to charging and discharging of the electricity storage device.

[0142] The electricity storage device, particularly the lithium ion secondary battery, manufactured as described above has high adhesion to the electrodes and is equipped with the separator of this embodiment having a small thermal shrinkage rate, and therefore has excellent battery characteristics (rate characteristics) and long-term continuous operation resistance (cycle characteristics). EXAMPLES

[0143] Hereinafter, the embodiments of the present disclosure will be specifically described with reference to examples and comparative examples, but the present disclosure is not limited to these examples and comparative examples.

[0144] Measurement and evaluation methods <Thickness of Coating Layer and Protruding Amount of Particulate Polymer> The separator was freeze-fractured, and the cross section was observed with an SEM (model S-4800, manufactured by HITACHI). The thickness of the thermoplastic polymer-containing layer was measured from the obtained field of view. In detail, a separator sample was cut to about 1.5 mm x 2.0 mm and stained with ruthenium. The stained sample and ethanol were placed in a gelatin capsule, frozen with liquid nitrogen, and then the sample was fractured with a hammer. The fractured sample was vapor-deposited with osmium and observed at an acceleration voltage of 1.0 kV and 30,000 times magnification. In the SEM image, the distance from the substrate-coating layer boundary to the outer surface of the coating layer in the inorganic filler part of the coating layer was measured as the thickness of the coating layer (μm). Note that the "inorganic filler part" refers to a part that is 1.5D or more away from each protruding particulate polymer, with D being the diameter of each protruding particulate polymer. The "diameter of each protruding particulate polymer" was measured as the diameter of a circle equivalent to the area. The thickness of the coating layer was measured at 20 points, and the average value was calculated. The maximum distance (μm) from the substrate-coating layer boundary to the contour of the particulate polymer in the coating layer where the particulate polymer protruded was measured. The maximum distance to the contour of the particulate polymer was measured at 20 points, and the average value was calculated. The protrusion amount (μm) of the particulate polymer was calculated by subtracting the thickness of the inorganic filler part of the coating layer from the maximum distance to the contour of the particulate polymer, and the ratio of the protrusion amount of the particulate polymer to the thickness of the inorganic filler part of the coating layer was calculated.

[0145] <180° peel strength> The surface of the separator cut to 2 mm x 7 mm opposite the coating layer to be measured was attached to a glass plate with double-sided tape, and tape (product name "Mending Tape MP-12", manufactured by 3M) was attached to the coating layer. 5 mm of the tip of the tape was peeled off, and a tensile test was performed using a tensile tester (model "AG-IS, SLBL-1kN, manufactured by Shimadzu Corporation) by clamping the tip of the tape with a chuck so that the tape was peeled off at an angle of 180° to the surface direction of the separator, and the tensile strength (N / m) was measured. The pulling speed at this time was 50 mm / sec, the temperature was 25 degrees, and the relative humidity was 40%.

[0146] <Gradient rate of coating layer> The separator was freeze-fractured, and the cross section was observed with an SEM (model S-4800, manufactured by HITACHI). The thickness of the thermoplastic polymer-containing layer was measured from the obtained field of view. In detail, a separator sample was cut to about 1.5 mm x 2.0 mm and stained with ruthenium. The stained sample and ethanol were placed in a gelatin capsule, frozen with liquid nitrogen, and then the sample was fractured with a hammer. The fractured sample was vapor-deposited with osmium and observed at an acceleration voltage of 1.0 kV and 30,000 times magnification. As shown in FIG. 2, in the SEM image of the fractured sample cross section, the distance from the boundary between the substrate and the coating layer to the outer surface of the coating layer in the inorganic filler part of the coating layer was measured as the thickness L1 (μm) of the inorganic filler part of the coating layer. The "inorganic filler part" refers to a part that is 1.5D or more away from each protruding particulate polymer, where D is the volume average particle diameter of the protruding particulate polymer. In addition, the maximum distance L2 (μm) from the substrate-coating layer boundary line to the outer surface of the inorganic filler of the coating layer formed on the slope, and the maximum distance L3 (μm) to the outline of the protruding particulate polymer were measured, and the slope rate L2 / L1 of the coating layer and the coverage rate of the protruding portion (L2-L1) / (L3-L1) were calculated. The slope rate L2 / L1 of the coating layer and the coverage rate of the protruding portion (L2-L1) / (L3-L1) were measured at 200 points, and the average values ​​were calculated.

[0147] <Contact ratio between protruding particulate polymer and substrate> The separator was freeze-fractured, and the cross section was confirmed by SEM (model S-4800, manufactured by HITACHI). The thickness of the thermoplastic polymer-containing layer was measured from the obtained field of view. In detail, a separator sample was cut to about 1.5 mm x 2.0 mm and stained with ruthenium. The stained sample and ethanol were placed in a gelatin capsule, frozen with liquid nitrogen, and then the sample was fractured with a hammer. The fractured sample was vapor-deposited with osmium and observed at an acceleration voltage of 1.0 kV and 30,000 times magnification. In the SEM image, of the particulate polymers protruding from the thickness of the inorganic filler part of the coating layer, the number of particles in contact with the substrate was counted for 200 particulate polymers having a fractured surface, and this was taken as the contact ratio between the protruding particulate polymer and the substrate.

[0148] <Proportion of the Number of Particulate Polymers Protruding from the Thickness of the Inorganic Filler Portion of the Coating Layer> The separator was freeze-fractured, and the cross section was observed with an SEM (model S-4800, manufactured by HITACHI). The thickness of the thermoplastic polymer-containing layer was measured from the obtained field of view. In detail, a separator sample was cut to about 1.5 mm x 2.0 mm and stained with ruthenium. The stained sample and ethanol were placed in a gelatin capsule, frozen with liquid nitrogen, and then the sample was fractured with a hammer. The fractured sample was vapor-deposited with osmium and observed at an acceleration voltage of 1.0 kV and 30,000 times magnification. 200 particulate polymers present on the fractured surface were observed in the SEM image, and the number of particulate polymers protruding from the thickness of the inorganic filler part of the coating layer was counted, and this was taken as the ratio of the number of particulate polymers protruding from the thickness of the inorganic filler part of the coating layer.

[0149] <Average number of adjacent particulate polymers> The surface of the osmium-deposited separator for power storage devices was subjected to elemental mapping using a scanning electron microscope (SEM) (model "SU-8220", Hitachi) and an energy dispersive X-ray spectroscopy (EDX) (model "ULTIM EXTREME", Oxford). At this time, secondary electrons were selected as the SEM detector, and mapping measurements of carbon atoms were performed at a magnification of 10,000 times with an acceleration transmission of 3 kV and 20 mapping accumulations. In mapping of carbon atoms, a part that was visually recognized as circular was considered to be one particulate polymer, and the number of particles with a distance between the outer edges of 0.2 μm or less was counted for all particulate polymers in one field of view. This measurement was performed in three fields of view, and the average of all the measured values ​​was taken as the average number of adjacent particulate polymers.

[0150] <Ratio of average particle size of protruding particulate polymer to average particle size of inorganic filler> The cross section of the separator for an osmium-deposited power storage device was observed with a scanning electron microscope (SEM) (model "S-4800", manufactured by HITACHI) at an accelerating voltage of 1.0 kV and 10,000 times magnification to measure. Specifically, the equivalent circle diameter of area was measured for 200 arbitrary inorganic filler particles, and the volume average particle diameter MV was calculated from these values ​​and used as the average particle diameter. Similarly, the SEM image of the cross section of the separator for an osmium-deposited power storage device was observed, and the equivalent circle diameter of area was measured for 200 particulate polymers protruding from the thickness of the inorganic filler part of the coating layer, and the volume average particle diameter MV was calculated from these values ​​and used as the average particle diameter. From the average particle diameter of the inorganic filler or the average particle diameter of the particulate polymer obtained by the above method, the ratio of the average particle diameter of the protruding particulate polymer to the average particle diameter of the inorganic filler was calculated.

[0151] <Number of polymer particles within a radius of 10 μm> The surface of the osmium-deposited separator for power storage devices was subjected to elemental mapping using a scanning electron microscope (SEM) (model "SU-8220", Hitachi) and an energy dispersive X-ray spectroscopy (EDX) (model "ULTIM EXTREME", Oxford). In this case, secondary electrons were selected as the SEM detector, and mapping measurements of carbon atoms were performed at a magnification of 50 million times with an acceleration transmission of 3 kV and 20 mapping accumulations. In the mapping of carbon atoms, a part that is visually recognized as circular is considered to be one particulate polymer, and the number of particulate polymers present within a radius of 10 μm from any particulate polymer was counted for all particulate polymers in one field of view, and the average value was calculated.

[0152] <Measurement of methylene chloride solubles> The methylene chloride soluble content in the substrate and separator was measured by the following method. The substrate or separator sampled to 100 x 100 mm was de-electrified and weighed using a precision balance (W0(g)). Next, 200 ml of methylene chloride was added to a sealed container, and the separator was immersed at room temperature for 15 minutes. The separator was then removed, dried at room temperature for 3 hours, de-electrified in the same manner as above, and weighed using a precision balance (W1(g)). The methylene chloride soluble content was calculated using the following formula. Methylene chloride solubles (%) = {(W1-W0) / W0} x 100

[0153] <Total amount of metal cations> 0.60 g of the separator was placed in a Teflon (registered trademark) pressure decomposition vessel, 10 ml of sulfuric acid was added, and the vessel was sealed and heated in an air bath at 200°C for 15 hours. After cooling, the solution in the vessel was transferred to a 100 ml resin measuring flask and diluted to volume to obtain a sample solution. The sample solution was measured using an inductively coupled plasma atomic emission spectrometry (ICP-OES) (model "ICPE-9000", manufactured by Shimadzu Corporation), and the content of each element was calculated using a calibration curve prepared from the standard solution.

[0154] <Heat shrinkage rate> As a sample, the multilayer porous membrane was cut into a size of 100 mm in the MD direction and 100 mm in the TD direction, and left to stand in an oven at 130°C or 150°C for 1 hour. At this time, the sample was sandwiched between two pieces of paper so that the hot air would not directly hit the sample. After removing the sample from the oven and cooling, the length (mm) was measured and the thermal shrinkage was calculated using the following formula. Measurements were performed in the MD direction and the TD direction, and the larger value was taken as the thermal shrinkage. Heat shrinkage rate (%) = {(100 - length after heating) / 100} x 100

[0155] <Porosity of the substrate> A sample of 10 cm x 10 cm square was cut from the substrate and its volume (cm 3 ) and mass (g). Using these values, the density of the substrate was calculated to be 0.95 (g / cm 3 ) and the porosity was calculated from the following formula. Porosity (%) = (1-mass / volume / 0.95) x 100

[0156] <Air permeability> The air permeability of the substrate and the separator for an electricity storage device was determined as the air permeability resistance measured in accordance with JIS P-8117 using a Gurley air permeability meter G-B2 (model name) manufactured by Toyo Seiki Co., Ltd. When the coating layer was present on only one side of the substrate, a needle could be pierced from the side where the coating layer was present.

[0157] <Thickness of substrate or separator> A 10 cm x 10 cm square sample was cut from the substrate or separator, and 9 points (3 points x 3 points) were selected in a grid pattern to measure the thickness (μm) using a micro thickness gauge (Toyo Seiki Seisakusho Co., Ltd., Type KBM) at room temperature of 23 ± 2°C. The average value of the measurements obtained at the 9 points was calculated as the thickness of the substrate or separator.

[0158] <Piercing strength> Using a handy compression tester KES-G5 (model name) manufactured by Kato Tech, the substrate was fixed with a sample holder with an opening diameter of 11.3 mm. Next, a puncture test was performed on the center of the fixed substrate using a needle with a tip curvature radius of 0.5 mm at a puncture speed of 2 mm / sec in an atmosphere of 25°C to measure the maximum puncture load. The maximum puncture load was converted to a value per 20 μm thickness and used as the puncture strength (gf / 20 μm). When the thermoplastic polymer is present only on one side of the substrate, the needle can be punctured from the side where the thermoplastic polymer is present.

[0159] <Average pore size of polyolefin microporous membrane> It is known that the fluid inside the capillary follows Knudsen flow when the mean free path of the fluid is larger than the pore diameter of the capillary, and follows Poiseuille flow when the mean free path is smaller. Therefore, it is assumed that the air flow in the air permeability measurement of the thermoplastic polymer-containing layer follows Knudsen flow, and the water flow in the water permeability measurement of the substrate follows Poiseuille flow.

[0160] The average pore size d (μm) of the polyolefin microporous membrane is expressed as the air permeation rate constant R gas (m 3 / (m 2 sec Pa), water permeation rate constant R liq (m 3 / (m 2 The following equation was used to calculate the viscosity of the thin film from the air pressure (m / sec), the molecular velocity of air (ν), the viscosity of water (η), the standard pressure (Ps) (=101325 Pa), the porosity (ε) (%), and the film thickness (L) (μm). d = 2ν × (R liq / R gas )×(16η / 3Ps)×10 6

[0161] Here, R gas was calculated from the air permeability (sec) using the following formula: R gas =0.0001 / (air permeability × (6.424 × 10 -4 )×(0.01276×101325))

[0162] Also, R liq is the permeability (cm 3 / (cm 2 The pressure was calculated using the following formula: R liq =water permeability / 100

[0163] The water permeability was determined as follows: A thermoplastic polymer-containing layer that had been soaked in ethanol beforehand was placed in a stainless steel liquid permeation cell with a diameter of 41 mm, and the ethanol in this layer was washed off with water. After that, water was allowed to pass through the layer at a pressure difference of about 50,000 Pa. The amount of water permeated (cm 3 ) the amount of water permeable per unit time, unit pressure and unit area was calculated, and this was taken as the permeability.

[0164] In addition, ν is the gas constant R (= 8.314), absolute temperature T (K), pi, and the average molecular weight of air M (= 2.896 × 10 -2 kg / mol) using the following formula: ν=((8R×T) / (π×M)) 1 / 2

[0165] Glass Transition Temperature of Thermoplastic Polymers An appropriate amount of the aqueous dispersion containing a thermoplastic polymer (solid content = 38 to 42 parts by mass, pH = 9.0) was placed in an aluminum dish and left to stand at room temperature for 24 hours to obtain a dry film. Approximately 17 mg of the dry film was filled into an aluminum container for measurement, and a DSC curve under a nitrogen atmosphere and a DSC curve were obtained using a DSC measurement device (Shimadzu Corporation, model name "DSC6220"). The measurement conditions were as follows. First stage heating program: Start at 30℃, heat up at a rate of 10℃ per minute. After reaching 150℃ Maintain for 5 minutes. Second stage temperature reduction program: Reduce temperature from 110℃ at a rate of 10℃ per minute. After reaching -50℃, maintain temperature for 5 minutes. Third stage heating program: Heat from -50°C to 150°C at a rate of 10°C per minute. DSC and DDSC data were obtained during this third stage heating. The glass transition temperature of the obtained DSC curve was determined by the method described in JIS-K 7121. Specifically, the glass transition temperature (Tg) was determined as the temperature at the point where a line extending the low-temperature side baseline of the DSC curve to the high-temperature side intersects with a line equidistant in the vertical direction from the line extending the high-temperature side baseline of the DSC curve to the low-temperature side, and the curve of the stepwise change in the glass transition.

[0166] <Aspect ratio of inorganic filler in coating layer> The surface of the osmium-deposited separator for a power storage device was observed at an acceleration voltage of 1.0 kV and 10,000 times magnification using a scanning electron microscope (SEM) (model "S-4800", manufactured by Hitachi). The aspect ratio was determined by image processing of the inorganic filler in the coating layer in the SEM image. Even when the inorganic fillers were bonded to each other, those in which the length and width of the inorganic filler alone could be clearly recognized were selected, and the aspect ratio was calculated based on these. Specifically, 10 inorganic fillers whose length and width were clearly recognized were selected, and the average value of the value obtained by dividing the long axis of each inorganic filler by the short axis of each inorganic filler was taken as the aspect ratio. When there were fewer than 10 inorganic fillers whose length and width could be clearly recognized in one field of view, 10 were selected from images of multiple fields of view.

[0167] <Particle size distribution of inorganic filler> The particle size distribution of the inorganic filler was measured using a particle size measuring device (manufactured by Nikkiso Co., Ltd., product name "Microtrac UPA150"). The sample solution to be measured was the pre-coating dispersion liquid, and the measurement conditions were loading index = 0.20 and measurement time 300 seconds. The particle size distribution (Cv value) of the inorganic filler was calculated by dividing the standard deviation SD value of the volume average particle size in the obtained data by the value of D50.

[0168] <Volume average particle diameter (D50) of thermoplastic polymer in aqueous dispersion and volume average particle diameter (D50) of resin binder> The volume average particle diameter (D50) of the thermoplastic polymer in the aqueous dispersion and the volume average particle diameter (D50) of the resin binder were measured using a particle diameter measuring device (manufactured by Nikkiso Co., Ltd., product name "Microtrac UPA150"). The measurement conditions were loading index = 0.20, measurement time 300 seconds, and the particle diameter (D50) value at which the cumulative volume in the obtained data becomes 50% was recorded as the volume average particle diameter (D50).

[0169] Particle size distribution of particulate polymer The cross section of the osmium-deposited separator for electricity storage devices was observed at an acceleration voltage of 1.0 kV and a magnification of 10,000 times using a scanning electron microscope (SEM) (model "S-4800", manufactured by Hitachi Corporation). Specifically, the area-equivalent circle diameter was measured for 200 arbitrary particulate polymers, and the number-average particle diameter MN and volume-average particle diameter MV were calculated from these values, and the particle size distribution of the particulate polymer was calculated as MV / MN.

[0170] Rate characteristics a. Preparation of the positive electrode The positive electrode active material was nickel, manganese, and cobalt composite oxide (NMC) (Ni:Mn:Co=1:1:1 (element ratio), density 4.70 g / cm 3 ) as a conductive additive, graphite powder (KS6) (density 2.26 g / cm 3 1.6 parts by mass of acetylene black powder (AB) (density 1.95 g / cm 3 3.8 parts by mass of 1.25% cellulose ether (1.0 parts by mass, number average particle diameter 48 nm), and polyvinylidene fluoride (PVdF) (density 1.75 g / cm3) as a binder. 3 ) were mixed in a ratio of 4.2 parts by mass, and dispersed in N-methylpyrrolidone (NMP) to prepare a slurry. This slurry was applied to one side of an aluminum foil having a thickness of 20 μm, which serves as a positive electrode current collector, using a die coater, and dried at 130° C. for 3 minutes, and then compression molded using a roll press to prepare a positive electrode. The amount of the positive electrode active material applied at this time was 109 g / m 2 It was.

[0171] b. Preparation of the negative electrode Graphite powder A (density 2.23 g / cm) was used as the negative electrode active material. 3 , number average particle diameter 12.7 μm) and 87.6 parts by mass of graphite powder B (density 2.27 g / cm 3A slurry was prepared by dispersing 9.7 parts by mass of ammonium salt of carboxymethylcellulose (number average particle diameter 6.5 μm) as a binder (solid content equivalent) (aqueous solution with a solid content concentration of 1.83 parts by mass) and 1.7 parts by mass of diene rubber latex (solid content equivalent) (aqueous solution with a solid content concentration of 40 parts by mass) in purified water. This slurry was applied to one side of a copper foil with a thickness of 12 μm to serve as a negative electrode current collector using a die coater, dried at 120° C. for 3 minutes, and then compression molded using a roll press machine to produce a negative electrode. The amount of negative electrode active material applied at this time was 5.2 g / m 2 It was.

[0172] c. Preparation of non-aqueous electrolyte A non-aqueous electrolyte solution was prepared by dissolving LiPF6 as a solute in a mixed solvent of ethylene carbonate:ethyl methyl carbonate=1:2 (volume ratio) to a concentration of 1.0 mol / L.

[0173] d. Battery assembly The separator or substrate was cut into a circle of 24 mmφ, and the positive and negative electrodes were cut into circles of 16 mmφ. The negative electrode, separator or substrate, and positive electrode were stacked in this order so that the active material surfaces of the positive and negative electrodes faced each other, and were then placed in a stainless steel metal container with a lid. The container and the lid were insulated, and the container was in contact with the copper foil of the negative electrode, and the lid was in contact with the aluminum foil of the positive electrode. 0.4 ml of the nonaqueous electrolyte was poured into the container and sealed to assemble a battery.

[0174] e. Rate characteristic evaluation The simplified battery assembled in d. was charged at 25°C with a current value of 3 mA (about 0.5 C) to a battery voltage of 4.2 V, and then the current value was tapered from 3 mA to maintain 4.2 V, for a total of about 6 hours after the battery was made. Then, it was discharged at a current value of 3 mA to a battery voltage of 3.0 V. Next, it was charged at 25°C with a current value of 6 mA (about 1.0 C) to a battery voltage of 4.2 V, and then the current value was tapered from 6 mA to maintain 4.2 V, for a total of about 3 hours. Then, the discharge capacity when it was discharged at a current value of 6 mA to a battery voltage of 3.0 V was taken as the 1C discharge capacity (mAh). Next, it was charged at 25°C with a current value of 6 mA (about 1.0 C) to a battery voltage of 4.2 V, and then the current value was tapered from 6 mA to maintain 4.2 V, for a total of about 3 hours. The discharge capacity when the battery was discharged at a current value of 12 mA (approximately 2.0 C) to a battery voltage of 3.0 V was defined as the 2C discharge capacity (mAh). The ratio of the 2C discharge capacity to the 1C discharge capacity was then calculated, and this value was defined as the rate characteristic. Rate characteristic (%) = (2C discharge capacity / 1C discharge capacity) x 100

[0175] Evaluation criteria for rate characteristics (%) A (Good): Rate characteristics are over 85% B (Acceptable): Rate characteristics are over 80% and 85% or less C (bad): Rate characteristics are 80% or less

[0176] <Adhesion strength with electrode (before electrolyte injection)> The separator was cut into a rectangular shape of 20 mm width x 70 mm length, and was layered on a positive electrode cut to a size of 15 mm x 60 mm to form a separator and electrode laminate, and this laminate was pressed under the following conditions. Temperature: 90℃ Press pressure: 1MPa Press time: 5 seconds The peel strength between the separator and the electrode after pressing was measured by a 90° peel test at a peel speed of 50 mm / min using force gauges ZP5N and MX2-500N (product name) manufactured by Imada Co., Ltd. At this time, the average value of the peel strength in the peel test for a length of 40 mm conducted under the above conditions was adopted as the peel strength. Adhesion Evaluation Criteria A (Good): Peel strength is 5N / m or more B (Acceptable): Peel strength is 2N / m or more and less than 5N / m C (poor): Peel strength is 1N / m or more and less than 2N / m D (Not acceptable): Peel strength is less than 1N / m

[0177] <Adhesion strength with electrode (after electrolyte injection)> The separator was cut into a rectangular shape of 20 mm wide x 70 mm long, and was stacked with a positive electrode cut to 15 mm x 60 mm to form a separator-electrode laminate. This laminate was inserted into an aluminum laminate film, and 0.4 ml of electrolyte (a mixture of EC / DEC = 1 / 2 containing 1 mol / L LiPF6) was added. This was sealed and left to stand for 12 hours, and pressed under the following conditions. Temperature: 90℃ Press pressure: 1MPa Press time: 1 minute The peel strength between the separator and the electrode after pressing was measured by a 90° peel test at a peel speed of 50 mm / min using force gauges ZP5N and MX2-500N (product name) manufactured by Imada Co., Ltd. At this time, the average value of the peel strength in the peel test for a length of 40 mm conducted under the above conditions was adopted as the peel strength. Adhesion Evaluation Criteria A (Good): Peel strength is 5N / m or more B (Acceptable): Peel strength is 2N / m or more and less than 5N / m C (poor): Peel strength is 1N / m or more and less than 2N / m D (Not acceptable): Peel strength is less than 1N / m

[0178] <Dust shedding> A tape (manufactured by 3M) measuring 12 mm wide and 100 mm long was attached to the raw polymer coating layer of the separator. The force required to peel the tape from the sample at a speed of 50 mm / min was measured using a 90° peel strength measuring device (manufactured by IMADA, product name IP-5N). Based on the measurement results, the adhesive strength was evaluated according to the following criteria. A (good): 59N / m (6gf / mm) or more B (tolerable): 40N / m or more and less than 59N / m C (bad): Less than 40N / m

[0179] <Cycle characteristics> a. Preparation of the positive electrode The positive electrode active material was nickel, cobalt, and aluminum composite oxide (NCA) (Ni:Co:Al = 90:5:5 (element ratio), density 3.50 g / cm 3 100 parts by mass of acetylene black powder (AB) as a conductive material, 1.25 parts by mass of acetylene black powder (AB) as a conductive material, and 1.0 part by mass of polyvinylidene fluoride (PVdF) as a binder were mixed and dispersed in N-methylpyrrolidone (NMP) to prepare a slurry. This slurry was applied to both sides of a 15 μm thick aluminum foil that serves as a positive electrode current collector using a die coater, dried at 130° C. for 3 minutes, and then compression molded using a roll press machine to prepare a positive electrode. The amount of positive electrode active material applied at this time was 456 g / m 2 It was.

[0180] b. Preparation of the negative electrode A slurry was prepared by dispersing 86.0 parts by mass of graphite powder as the negative electrode active material, 4.5 parts by mass of silicon oxide (SiO), and 1 part by mass of sodium salt of carboxymethylcellulose and 1.0 part by mass of styrene-butadiene rubber (SBR) as the binder in purified water. This slurry was applied to both sides of a 7.5 μm-thick copper foil serving as a negative electrode current collector using a die coater, dried at 120° C. for 3 minutes, and then compression molded using a roll press machine to prepare a negative electrode. The amount of negative electrode active material applied at this time was 266 g / m 2 It was.

[0181] c. Preparation of non-aqueous electrolyte A non-aqueous electrolyte solution was prepared by dissolving LiPF6 as a solute in a mixed solvent of ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate = 25: 70: 5 (weight ratio) to a concentration of 1.4 mol / L.

[0182] d. Battery assembly A positive electrode (width 63 mm), a negative electrode (width 64 mm), and a separator (width 67 mm) were stacked and spirally wound to prepare a wound body, which was then placed in a cylindrical battery can with an outer diameter of 21 mm and a height of 70 mm, and the nonaqueous electrolyte was poured into the can and sealed to assemble the battery.

[0183] e. Evaluation of cycle characteristics The battery assembled in d. was charged at 25°C at a current value of 3 mA (about 0.5 C) until the battery voltage reached 4.2 V, and then charged until the current value reached 50 mA while maintaining 4.2 V. Thereafter, the battery was discharged at 0.2 C until the battery voltage reached 2.5 V, and the initial capacity was determined. Next, the battery was charged at 0.3 C until the battery voltage reached 4.2 V, and then charged until the current value reached 50 mA while maintaining 4.2 V, and then discharged at 1 C until the battery voltage reached 2.5 V. This constituted one cycle, and charging and discharging were repeated. The cycle characteristics were evaluated according to the following criteria, using the capacity retention rate after 500 cycles relative to the initial capacity (capacity at the first cycle). A: Capacity retention rate of 80% or more B: Capacity retention rate of 75% or more but less than 80% C: Capacity retention rate of less than 75%

[0184] <<Examples of substrate manufacturing>> <Production of polyolefin microporous membrane B1> 45 parts by mass of homopolymer high density polyethylene with Mv of 700,000, 45 parts by mass of homopolymer high density polyethylene with Mv of 300,000, and 10 parts by mass of a mixture of homopolymer polypropylene with Mv of 400,000 and homopolymer polypropylene with Mv of 150,000 (mass ratio = 4:3) were dry blended using a tumbler blender. 1 part by mass of tetrakis-[methylene-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane was added as an antioxidant to 99 parts by mass of the obtained polyolefin mixture, and the mixture was dry blended again using a tumbler blender to obtain a mixture. The obtained mixture was fed to a twin-screw extruder by a feeder under a nitrogen atmosphere. Liquid paraffin (dynamic viscosity at 37.78 °C 7.59 × 10 -5 m 2 / s) was injected into the extruder cylinder by a plunger pump. The operating conditions of the feeder and pump were adjusted so that the proportion of liquid paraffin in 100 parts by mass of the total mixture to be extruded was 65 parts by mass, that is, the proportion of the resin composition was 35 parts by mass.

[0185] Next, they were melt-kneaded in a twin-screw extruder while being heated to 230°C, and the resulting melt-kneaded product was extruded through a T-die onto a cooling roll controlled at a surface temperature of 80°C, and the extrudate was cast by contacting the cooling roll and cooled to solidify, thereby obtaining a sheet-like molded product. This sheet was stretched at a ratio of 7x6.4 times at a temperature of 112°C using a simultaneous biaxial stretching machine, and then immersed in methylene chloride to extract and remove liquid paraffin, and then dried and stretched 2 times in the transverse direction at a temperature of 130°C using a tenter stretching machine. Then, this stretched sheet was relaxed by about 10% in the width direction and heat-treated to obtain a polyolefin microporous membrane B1 as a substrate.

[0186] The properties of the obtained microporous polyolefin membrane B1 were measured and evaluated by the above-mentioned methods. The results are shown in Table 1.

[0187] <Production of polyolefin microporous membranes B2 to B4> Polyolefin microporous membrane B2 was produced in the same manner as polyolefin microporous membrane B1, except that the extrusion amounts of the resin composition and liquid paraffin, and the temperature and relaxation rate during stretching were changed. Polyolefin microporous membranes B3 and B4 were produced in the same manner as polyolefin microporous membrane B1, except that the methylene chloride temperature during immersion in methylene chloride was adjusted. The results of measurement and evaluation of polyolefin microporous membranes B2 to B4 in the same manner are shown in Table 1.

[0188] <Polyolefin microporous membrane B5> A polyolefin microporous membrane B5 was prepared by using a polyolefin microporous membrane B1, which was measured and evaluated in the same manner as for the polyolefin microporous membrane B1. The results are shown in Table 1.

[0189] [Table 1]

[0190] <Preparation Example of Water Dispersion> Preparation of Water Dispersion A1 Into a reaction vessel equipped with a stirrer, reflux condenser, dropping tank, and thermometer, 70.4 parts by mass of ion-exchanged water, 0.5 parts by mass of "Aqualon KH1025" (registered trademark, 25% aqueous solution manufactured by Daiichi Kogyo Seiyaku Co., Ltd., indicated as "KH1025" in the table; the same applies below), and 0.5 parts by mass of "ADEKA REASOAP SR1025" (registered trademark, manufactured by ADEKA Corporation, 25% aqueous solution, indicated as "SR1025" in the table; the same applies below) were added, and the temperature inside the reaction vessel was raised to 95°C. Thereafter, while maintaining the temperature inside the vessel at 95°C, 7.5 parts by mass of ammonium persulfate (2% aqueous solution) (indicated as "APS(aq)" in the table; the same applies below) was added.

[0191] On the other hand, a mixture of 71.5 parts by mass of methyl methacrylate (MMA), 18.9 parts by mass of n-butyl acrylate (BA), 2 parts by mass of 2-ethylhexyl acrylate (EHA), 0.1 parts by mass of methacrylic acid (MAA), 0.1 parts by mass of acrylic acid (AA), 2 parts by mass of 2-hydroxyethyl methacrylate (HEMA), 5 parts by mass of acrylamide (AM), 0.4 parts by mass of glycidyl methacrylate (GMA), 0.4 parts by mass of trimethylolpropane triacrylate (A-TMPT) (manufactured by Shin-Nakamura Chemical Co., Ltd.), 0.3 parts by mass of γ-methacryloxypropyltrimethoxysilane (AcSi), 3 parts by mass of KH1025, 3 parts by mass of SR1025, 0.05 parts by mass of sodium p-styrenesulfonate (NaSS), 7.5 parts by mass of ammonium persulfate (2% aqueous solution), and 52 parts by mass of ion-exchanged water was mixed for 5 minutes with a homomixer to prepare an emulsion. The obtained emulsion was dropped from the dropping tank into the reaction vessel. Dropping started 5 minutes after the aqueous ammonium persulfate solution was added to the reaction vessel, and the entire amount of the emulsion was dropped over 150 minutes. During the drop of the emulsion, the temperature inside the vessel was maintained at 80°C. At this time, the stirring bar inserted in the reaction vessel was constantly stirred with a magnetic stirrer.

[0192] After the dropwise addition of the emulsified liquid was completed, the temperature inside the reaction vessel was maintained at 80°C for 90 minutes, and then cooled to room temperature to obtain an emulsion. The obtained emulsion was adjusted to pH=9.0 using an aqueous ammonium hydroxide solution (25% aqueous solution) to obtain an acrylic copolymer latex with a concentration of 40 parts by mass (aqueous dispersion A1). The glass transition temperature (Tg) and volume average particle size (D50) of the thermoplastic polymer contained in the obtained aqueous dispersion A1 were evaluated by the above-mentioned method. The obtained results are shown in Table 2.

[0193] Preparation of Water Dispersions A2 to A4 Water dispersions A2 to A4 were obtained and their physical properties were evaluated in the same manner as for water dispersion A1, except that the composition of the emulsion was changed as shown in Table 2. The obtained results are shown in Table 2.

[0194] Preparation of Water Dispersion A2-1 A part of the aqueous dispersion A1 was taken, and multi-stage polymerization was carried out using this as a seed polymer to synthesize the aqueous dispersion A2-1. Specifically, a mixture of 20 parts by mass of the aqueous dispersion A1 in terms of solid content and 70.4 parts by mass of ion-exchanged water was first put into a reaction vessel equipped with a stirrer, a reflux condenser, a dropping tank, and a thermometer, and the temperature inside the reaction vessel was raised to 80°C. Then, while maintaining the temperature inside the vessel at 80°C, 7.5 parts by mass of ammonium persulfate (2% aqueous solution) was added. This is the initial charge.

[0195] On the other hand, a mixture of 71.5 parts by mass of methyl methacrylate (MMA), 18.9 parts by mass of n-butyl acrylate (BA), 2 parts by mass of 2-ethylhexyl acrylate (EHA), 0.1 parts by mass of methacrylic acid (MAA), 0.1 parts by mass of acrylic acid (AA), 2 parts by mass of 2-hydroxyethyl methacrylate (HEMA), 5 parts by mass of acrylamide (AM), 0.4 parts by mass of glycidyl methacrylate (GMA), 0.7 parts by mass of trimethylolpropane triacrylate (A-TMPT), 0.3 parts by mass of γ-methacryloxypropyltrimethoxysilane (AcSi), 3 parts by mass of KH1025, 3 parts by mass of SR1025, 0.05 parts by mass of sodium p-styrenesulfonate (NaSS), 7.5 parts by mass of ammonium persulfate (2% aqueous solution), and 52 parts by mass of ion-exchanged water was mixed for 5 minutes with a homomixer to prepare an emulsion. The obtained emulsion was dropped from the dropping tank into the reaction vessel. Dropping started 5 minutes after the aqueous ammonium persulfate solution was added to the reaction vessel, and the entire amount of the emulsion was dropped over 150 minutes. During the drop of the emulsion, the temperature inside the vessel was maintained at 80°C. At this time, the stirring bar inserted in the reaction vessel was constantly stirred with a magnetic stirrer.

[0196] After the emulsion was dropped, the temperature inside the reaction vessel was kept at 80° C. while stirring for 90 minutes, and then cooled to room temperature to obtain an emulsion. The obtained emulsion was adjusted to pH=9.0 using an aqueous ammonium hydroxide solution (25% aqueous solution) to obtain an acrylic copolymer latex with a concentration of 40 parts by mass (aqueous dispersion A2-1). The obtained aqueous dispersion A2-1 was evaluated by the above-mentioned method. The obtained results are shown in Table 2.

[0197] Preparation of Water Dispersions A1-2 to A1-4 By adjusting the number of multi-stage polymerizations, copolymer latexes (water dispersions A1-2 to A1-4) were obtained. The obtained water dispersions were each evaluated by the above-mentioned methods. The obtained results are shown in Table 2.

[0198] Preparation of Aqueous Dispersions A2-1, A3-1 to A3-4, and A4-1 Copolymer latexes (water dispersions A2-1, A3-1 to A3-4, and A4-1) were obtained in the same manner as for the water dispersion A1-1, except that the composition of the seed polymer, monomer, and other raw materials, the number of multi-stage polymerizations, and the polymerization conditions were changed as shown in Table 2. The obtained water dispersions were each evaluated by the above-mentioned method. The obtained results are shown in Table 2.

[0199] <Aqueous dispersion A5~A6> SB latex (Tg: 33°C, particle size: 300 nm, toluene insoluble content: 95%, swelling ratio: 1.4 times) was used as water dispersion A5. PVdF-HFP (product name LBG, Arkema) with a primary particle size of 200 nm and agglomerated to form secondary particles of 2030 nm was used as water dispersion A6.

[0200] [Table 2] ·emulsifier KH1025: "Aqualon KH1025" registered trademark, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., 25% aqueous solution SR1025: "ADEKA REASOAP SR1025" registered trademark, manufactured by ADEKA Corporation, 25% aqueous solution NaSS: Sodium p-styrenesulfonate Initiator APS(aq): Ammonium persulfate (2% aqueous solution) Monomer MAA: Methacrylic acid AA: Acrylic acid MMA: Methyl methacrylate BA: n-butyl acrylate BMA: n-butyl methacrylate EHA: 2-Ethylhexyl acrylate CHMA: Cyclohexyl methacrylate St: styrene AN: Acrylonitrile HEMA: 2-hydroxyethyl methacrylate AM: Acrylamide GMA: glycidyl methacrylate A-TMPT: Trimethylolpropane triacrylate AcSi: γ-methacryloxypropyltrimethoxysilane

[0201] <Separator manufacturing example> Example 1 0.3 parts by mass of an aqueous solution of ammonium polycarboxylate (SN Dispersant 5468 manufactured by San Nopco) and 100 parts by mass of aluminum oxide hydroxide (boehmite) as an inorganic filler were mixed with 100 parts by mass of water, and the mixture was processed with a bead mill to obtain a pre-coating dispersion. 1 part by mass of carboxymethylcellulose (CMC) as a water-soluble polymer component was mixed with 100 parts by mass of inorganic filler to the pre-coating dispersion, and then 4 parts by mass of an acrylic latex suspension (solid concentration 40%, volume average particle size 150 nm) as a resin binder was mixed in a ratio of 20 parts by mass of water dispersion A1-2 as a solid content, and the mixture was uniformly dispersed to prepare a coating liquid (solid content 40 parts by mass) containing a thermoplastic polymer.

[0202] Both sides of the polyolefin microporous membrane B1 were subjected to a surface treatment by corona discharge treatment. Then, a coating solution was applied to one side (side (A)) of the polyolefin microporous membrane B1 using a gravure coater. The shear rate of the gravure coater was 80,000 sec -1The coating area ratio of the coating layer to the polyolefin microporous membrane at this time was 100%. The coating liquid after application was then dried at 60°C to remove water. Furthermore, the coating liquid was similarly applied to the surface (surface (B)) opposite to the surface (A) of the polyolefin microporous membrane B1, and dried again in the same manner as above. In this way, a separator having coating layers formed on both surfaces of the polyolefin microporous membrane B1 was obtained.

[0203] Examples 2 to 20 Separators were obtained in the same manner as in Example 1, except that the polyolefin microporous membrane, the composition of the coating solution, the coating conditions, etc. were changed as shown in Tables 3 and 4, respectively.

[0204] Comparative Examples 1 to 9 Separators of Comparative Examples 1 to 9 were obtained in the same manner as in Example 1, except that the polyolefin microporous membrane, the composition of the coating solution, the coating conditions, etc. were changed as shown in Table 5. In the separator of Comparative Example 6, the particulate polymer was dispersed in the form of secondary particles. As the alumina of Comparative Example 9, "AKP3000" manufactured by Sumitomo Chemical Co., Ltd. was used.

[0205] Table 6 shows the results of evaluating the cycle characteristics of the separators of Examples 16, 19, and 20, and Comparative Examples 1 and 3. In the case of Comparative Example 3, distortion occurred in the electrode-separator winding after the cycle characteristics test.

[0206] [Table 3]

[0207] [Table 4]

[0208] [Table 5]

[0209] [Table 6] [Industrial Applicability]

[0210] The separator for an electricity storage device according to the present disclosure can be suitably used in various electricity storage devices, preferably lithium ion secondary batteries. [Explanation of symbols]

[0211] 1. Inorganic filler 2 Particulate polymer 10 Base material 20 Covering layer

Claims

1. A separator for an electricity storage device, comprising: a substrate which is a polyolefin microporous film containing a polyolefin as a main component; and a coating layer disposed on at least one surface of the substrate, The coating layer includes an inorganic filler and a particulate polymer of a thermoplastic polymer, In the coating layer, the amount of the particulate polymer is 1 part by mass or more and 50 parts by mass or less with respect to 100 parts by mass of the inorganic filler contained in the coating layer, the particulate polymer includes particulate polymer protruding from the coating layer by 0.1 times or more the thickness of the inorganic filler portion of the coating layer, The coating layer is formed in a gradient shape so as to become thicker toward the protruding particulate polymer, A separator for an electric storage device, in which, when a thickness of an inorganic filler portion of the coating layer is L1 and a maximum distance from a boundary line between the substrate and the coating layer to an outer surface of the inorganic filler of the coating layer formed in the inclined shape is L2, an average value of a slope ratio L2 / L1 of the coating layer is 1.1 or more.

2. The separator for an electric storage device according to claim 1 , wherein an average value of the gradient ratio L2 / L1 of the coating layer is 1.2 or more.

3. 3. The separator for an electric storage device according to claim 1, wherein the average value of the coverage rate (L2-L1) / (L3-L1) of the protruding portions of the protruding particulate polymer is 0.4 or more, where L1 is a thickness of the inorganic filler portion of the coating layer, L2 is a maximum distance from the boundary line between the substrate and the coating layer to an outer surface of the inorganic filler of the coating layer formed in the inclined shape, and L3 is a maximum distance from the boundary line between the substrate and the coating layer to an outline of the protruding particulate polymer.

4. A separator for an electricity storage device, comprising: a substrate which is a polyolefin microporous film containing a polyolefin as a main component; and a coating layer disposed on at least one surface of the substrate, The coating layer includes an inorganic filler and a particulate polymer of a thermoplastic polymer, In the coating layer, the amount of the particulate polymer is 1 part by mass or more and 50 parts by mass or less with respect to 100 parts by mass of the inorganic filler contained in the coating layer, the particulate polymer includes particulate polymer protruding from the coating layer by 0.1 times or more the thickness of the inorganic filler portion of the coating layer, A separator for an electricity storage device, wherein 20% or more of the protruding particulate polymer is in contact with a surface of the substrate.

5. A separator for an electricity storage device, comprising: a substrate which is a polyolefin microporous film containing a polyolefin as a main component; and a coating layer disposed on at least one surface of the substrate, The coating layer includes an inorganic filler and a particulate polymer of a thermoplastic polymer, In the coating layer, the amount of the particulate polymer is 1 part by mass or more and 50 parts by mass or less with respect to 100 parts by mass of the inorganic filler contained in the coating layer, the particulate polymer includes particulate polymer protruding from the coating layer by 0.1 times or more the thickness of the inorganic filler portion of the coating layer, The separator for an electricity storage device, wherein the coating layer has a 180° peel strength from the substrate of 200 gf / cm or more.

6. A separator for an electricity storage device, comprising: a substrate which is a polyolefin microporous film containing a polyolefin as a main component; and a coating layer disposed on at least one surface of the substrate, The coating layer includes an inorganic filler and a particulate polymer of a thermoplastic polymer, In the coating layer, the amount of the particulate polymer is 1 part by mass or more and 50 parts by mass or less with respect to 100 parts by mass of the inorganic filler contained in the coating layer, the particulate polymer includes particulate polymer protruding from the coating layer by 0.1 times or more the thickness of the inorganic filler portion of the coating layer, A separator for an electricity storage device, wherein the average number of said protruding particulate polymers adjacent to any one of said protruding particulate polymers is less than two.

7. A separator for an electricity storage device, comprising: a substrate which is a polyolefin microporous film containing a polyolefin as a main component; and a coating layer disposed on at least one surface of the substrate, The coating layer includes an inorganic filler and a particulate polymer of a thermoplastic polymer, In the coating layer, the amount of the particulate polymer is 1 part by mass or more and 50 parts by mass or less with respect to 100 parts by mass of the inorganic filler contained in the coating layer, the particulate polymer includes particulate polymer protruding from the coating layer by 0.1 times or more the thickness of the inorganic filler portion of the coating layer, a ratio of an average particle diameter of the protruding particulate polymer to an average particle diameter of the inorganic filler is greater than 10; The particulate polymer has a particle size distribution MV / MN of 1.01 or more and 1.6 or less, the particle size distribution being calculated by dividing the volume average particle size MV of the particulate polymer by the number average particle size MN of the particulate polymer.

8. 8. The separator for an electricity storage device according to claim 1, wherein the number of the protruding particulate polymers is 50% or more of the total number of the particulate polymers contained in the coating layer.

9. The separator for an electric storage device according to any one of claims 1 to 8, wherein the number of other protruding particulate polymers present within a radius of 10 µm from any one of the protruding particulate polymers is less than 60.

10. The separator for use in an electricity storage device according to any one of claims 1 to 9, wherein a methylene chloride soluble matter in the separator for use in an electricity storage device is 0.05 parts by mass or more and 0.80 parts by mass or less with respect to a total mass of the separator for use in an electricity storage device.

11. 11. The power storage device separator according to claim 1, wherein a total amount of metal cations contained in the coating layer is 0.1 ppm or more and 100 ppm or less based on the total mass of the coating layer.

12. The separator for an electricity storage device according to any one of claims 1 to 11, wherein the coating layer contains a water-soluble polymer.

13. The electricity storage device separator according to claim 12 , wherein a content of the water-soluble polymer is 0.04 parts by mass or more and less than 2 parts by mass with respect to 100 parts by mass of the inorganic filler.

14. The separator for an electricity storage device according to any one of claims 1 to 13, wherein the thickness of one of the coating layers disposed on at least one of the substrates is 0.3 µm or more and 1.3 µm or less.

15. The separator for an electricity storage device according to any one of claims 1 to 14, wherein the particulate polymer comprises at least one selected from the group consisting of a copolymer containing a (meth)acrylate as a monomer, a styrene-butadiene copolymer, and a copolymer containing a fluorine atom.

16. The separator for an electrical storage device according to any one of claims 1 to 15, wherein the particulate polymer comprises a copolymer containing (meth)acrylic acid, butyl (meth)acrylate, and ethylhexyl (meth)acrylate as monomers.

17. The power storage device separator according to any one of claims 1 to 16, wherein the particulate polymer comprises a copolymer containing a polyfunctional (meth)acrylate as a monomer.

18. The separator for an electricity storage device according to any one of claims 1 to 17, wherein the particulate polymer is a primary particle.

19. The separator for use in an electricity storage device according to claim 18 , wherein the average particle size of the primary particles is 1 μm or more and 10 μm or less.

20. The separator for an electricity storage device according to any one of claims 1 to 19, which has a thermal shrinkage rate in the TD direction of 5% or less at 130°C for 1 hour.

21. The separator for an electricity storage device according to any one of claims 1 to 20, which has a thermal shrinkage rate in the TD direction of 5% or less at 150°C for 1 hour.

22. An electricity storage device comprising the separator for an electricity storage device according to any one of claims 1 to 21.

Citation Information

Patent Citations

  • Lithium ion battery composite membrane and preparation method thereof

    CN105958000A

  • Separator for power storage device

    JP2017107851A

  • Separator for lithium secondary battery and a method of making the same

    KR1020160118979A

  • Lithium ion battery separator

    WO2019089492A1

  • Functional layer for electrochemical elements, separator with functional layer for electrochemical elements, and electrochemical element

    WO2020175079A1

Cited By

  • Multilayer porous film, electrode body and non-aqueous secondary battery

    JP2023152737A